Lithium-based solid electrolyte, inorganic solid electrolyte, method for producing lithium-based solid electrolyte, modified positive electrode active material, modified negative electrode active material, all-solid-state secondary battery, electrode sheet for all-solid-state secondary battery, solid electrolyte sheet, electrode for all-solid-state secondary battery
Patent Information
- Application Number
- JP2022566953
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-30
- Filing Date
- 2021-12-01
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-12-01
AI Technical Summary
【0008】 本発明によれば、イオン伝導性に優れたリチウム系固体電解質を提供できる。 また、本発明によれば、無機固体電解質、リチウム系固体電解質の製造方法、修飾正極活物質、修飾負極活物質、全固体二次電池、全固体二次電池用電極シート、固体電解質シート、および、全固体二次電池用電極も提供できる。
Smart Images

Figure 0007634240000015 
Figure 0007634240000016 
Figure 0007634240000017
Description
[Technical field]
[0001] The present invention relates to a lithium-based solid electrolyte, an inorganic solid electrolyte, a method for producing a lithium-based solid electrolyte, a modified positive electrode active material, a modified negative electrode active material, an all-solid-state secondary battery, an electrode sheet for an all-solid-state secondary battery, a solid electrolyte sheet, and an electrode for an all-solid-state secondary battery. [Background technology]
[0002] Conventionally, liquid electrolytes with high ionic conductivity have been used in lithium-ion secondary batteries. However, liquid electrolytes are flammable, which poses safety issues. In addition, because they are liquid, they are difficult to compact, and there are limitations on capacity when the battery is enlarged. On the other hand, all-solid-state lithium-ion secondary batteries are one of the next-generation batteries that can solve these problems. In all-solid-state batteries, a solid electrolyte with good ionic conductivity is required to obtain the desired charge / discharge characteristics. For example, Patent Document 1 discloses a solid electrolyte that can be used in all-solid-state lithium-ion secondary batteries. Patent Document 1 discloses a solid electrolyte based on a lithium-containing oxide. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-052755 A Summary of the Invention [Problem to be solved by the invention]
[0004] In Patent Document 1, the conductivity is 10 -5 S cm -1 However, in recent years, there has been a demand for even higher conductivity.
[0005] An object of the present invention is to provide a lithium-based solid electrolyte having excellent ion conductivity. Another object of the present invention is to provide an inorganic solid electrolyte, a method for producing a lithium-based solid electrolyte, a modified positive electrode active material, a modified negative electrode active material, an all-solid-state secondary battery, an electrode sheet for an all-solid-state secondary battery, a solid electrolyte sheet, and an electrode for an all-solid-state secondary battery. [Means for solving the problem]
[0006] The present inventors have conducted extensive research to solve the above problems and have completed the present invention having the following configuration.
[0007] (1) A lithium-based solid electrolyte comprising amorphous lithium tetraborate, water, and a lithium salt. (2) A lithium-based solid electrolyte comprising mechanically milled lithium tetraborate, water, and a lithium salt. (3) the molar ratio of the lithium salt to lithium tetraborate is 0.001 to 1.5; The lithium-based solid electrolyte according to (1), wherein the molar ratio of water to lithium tetraborate is 3 to 15. (4) the molar ratio of the lithium salt to lithium tetraborate is 0.001 to 1.5; The lithium-based solid electrolyte according to (2), wherein the molar ratio of water to lithium tetraborate is 3 to 15. (5) Amorphous LiB3O5, Li3B 11 O 18 or Li3BO 12 a lithium-based solid electrolyte comprising: water; and a lithium salt. (6) The lithium-based solid electrolyte according to any one of (1) to (5), wherein the lithium salt is a compound represented by the formula (1) described below. (7) A lithium-based solid electrolyte, The lithium-based solid electrolyte contains Li, B, and O, The lithium-based solid electrolyte further contains two or more specific elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N; the molar ratio of B to Li is greater than 1.50 and less than 2.43; the molar ratio of O to Li is greater than 2.34 and less than 6.86; A lithium-based solid electrolyte having a molar ratio of each specific element to Li that is greater than 0.001 and less than 0.17. (8) A lithium-based solid electrolyte, The lithium-based solid electrolyte contains Li, B, and O, The lithium-based solid electrolyte further contains two or more specific elements selected from the group consisting of Group 4 elements of the periodic table, Group 15 elements of the periodic table, Group 16 elements of the periodic table, Group 17 elements of the periodic table, Si, C, Sc, Y, and H; When the molar amount of B in the lithium-based solid electrolyte is taken as 4.00, the molar amounts of Li, O, and a specific element are expressed as follows: The molar amount of Li is 1.58 to 3.49, The molar amount of O is 6.23 to 25.00; A lithium-based solid electrolyte in which the molar amount of each specific element is 0.001 to 10.00. (9) Infrared absorption spectrum: 800-1600 cm -1 The maximum absorption intensity in the wavenumber region of 3000 to 3500 cm -1 The lithium-based solid electrolyte according to any one of (1) to (8), wherein a ratio of maximum absorption intensities in the wave number region of (1) to (8) is 1 / 5 or more. (10) A lithium-based solid electrolyte containing Li, B, and O and satisfying any of the requirements X to Z described below. (11) The lithium-based solid electrolyte according to (10), further comprising one or more specific elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N. (12) Solid 7 The solid-state Li-NMR spectrum obtained at 20°C shows a chemical shift of -100 to +100 ppm in the full width at half maximum of the peak. 7The lithium-based solid electrolyte according to any one of (1) to (11), wherein a ratio of a full width at half maximum of a peak appearing in a chemical shift range of −100 to +100 ppm in a spectrum obtained by Li-NMR measurement at 120° C. is 50% or less. (13) Solid 7 The lithium-based solid electrolyte according to any one of (1) to (12), wherein, when a first peak appearing in the range of -100 to +100 ppm in a spectrum obtained by Li-NMR measurement at 20°C is subjected to waveform separation, the lithium-based solid electrolyte has a second peak in the chemical shift range of -3 to 3 ppm and a full width at half maximum of 5 ppm or less, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more. (14) Raman spectrum from 600 to 850 cm -1 (8) The lithium-based solid electrolyte according to (7), wherein the coefficient of determination obtained by linear regression analysis using the least squares method in a wave number region of 0.9400 or more. (15) The lithium-based solid electrolyte according to (7), which has a mass loss rate of 20 to 40% by mass when heated to 800° C. (16) An inorganic solid electrolyte having ion conductivity of an element selected from the group consisting of metal elements belonging to Group 1 of the periodic table and elements belonging to Group 2 of the periodic table, The inorganic solid electrolyte contains an element selected from the group consisting of metal elements belonging to Group 1 of the periodic table and elements belonging to Group 2 of the periodic table, B, and O; the inorganic solid electrolyte further contains two or more specific elements selected from the group consisting of Group 3 elements of the periodic table, Group 4 elements of the periodic table, Group 13 elements of the periodic table, Group 14 elements of the periodic table, Group 15 elements of the periodic table, Group 16 elements of the periodic table, Group 17 elements of the periodic table, and H; The inorganic solid electrolyte is amorphous, An inorganic solid electrolyte that satisfies requirement R described below. (17) An inorganic solid electrolyte comprising: a compound containing an element selected from the group consisting of a metal element belonging to Group 1 of the periodic table and an element belonging to Group 2 of the periodic table, B, and O; water; and a salt containing an element selected from the group consisting of a metal element belonging to Group 1 of the periodic table and an element belonging to Group 2 of the periodic table. (18) The inorganic solid electrolyte according to (17), wherein the compound is amorphous. (19) A method for producing the lithium-based solid electrolyte according to any one of (1) to (15), comprising the steps of: A step 1 of subjecting a lithium-based oxide containing Li and B to a mechanical milling treatment; Step 2 is mixing the product obtained in step 1 with water; and step 3 of removing water from the dispersion obtained in step 2 to obtain a lithium-based solid electrolyte. A method for producing a lithium-based solid electrolyte, which satisfies any one of requirements 1 to 3 described below. (20) Requirement 1 is met; The method for producing a lithium-based solid electrolyte according to (19), further comprising, before the step 1, a step 0 of subjecting a lithium-based oxide containing Li and B to a mechanical milling treatment in an environment in which a specific element source is not present. (21) A positive electrode comprising a positive electrode active material and a coating layer disposed on the positive electrode active material, A modified positive electrode active material, the coating layer of which contains the lithium-based solid electrolyte according to any one of (1) to (15) or the inorganic solid electrolyte according to any one of (16) to (18). (22) A negative electrode battery comprising: a negative electrode active material; and a coating layer disposed on the negative electrode active material; A modified negative electrode active material, the coating layer of which contains the lithium-based solid electrolyte according to any one of (1) to (15) or the inorganic solid electrolyte according to any one of (16) to (18). (23) An all-solid-state secondary battery including a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer in this order, An all-solid-state secondary battery, in which at least one of a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer contains the lithium-based solid electrolyte according to any one of (1) to (15) or the inorganic solid electrolyte according to any one of (16) to (18). (24) An electrode sheet for an all-solid-state secondary battery, comprising the lithium-based solid electrolyte according to any one of (1) to (15) or the inorganic solid electrolyte according to any one of (16) to (18). (25) A solid electrolyte sheet comprising the lithium-based solid electrolyte according to any one of (1) to (15) or the inorganic solid electrolyte according to any one of (16) to (18). (26) An electrode for an all-solid-state secondary battery, comprising: an active material; and an active material layer containing the lithium-based solid electrolyte according to any one of (1) to (15) or the inorganic solid electrolyte according to any one of (16) to (18); and a current collector. Effect of the Invention
[0008] According to the present invention, a lithium-based solid electrolyte having excellent ion conductivity can be provided. The present invention also provides an inorganic solid electrolyte, a method for producing a lithium-based solid electrolyte, a modified positive electrode active material, a modified negative electrode active material, an all-solid-state secondary battery, an electrode sheet for an all-solid-state secondary battery, a solid electrolyte sheet, and an electrode for an all-solid-state secondary battery. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a diagram showing an example of a spectrum obtained when solid-state 7Li-NMR (Nuclear Magnetic Resonance) measurement of a first embodiment of the lithium-based solid electrolyte of the present invention is carried out at 20° C. or 120° C. [Diagram 2] FIG. 2 is a diagram showing an example of a spectrum obtained when solid-state 7Li-NMR measurement of lithium tetraborate crystal is performed at 20° C. or 120° C. [Diagram 3] FIG. 3 is a diagram showing an example of a spectrum obtained when solid-state 7Li-NMR measurement of the first embodiment of the lithium-based solid electrolyte of the present invention was carried out at 20° C. [Figure 4] FIG. 4 is a diagram showing the waveform separation of the peaks shown in FIG. [Diagram 5] FIG. 5 is a diagram showing an example of a Raman spectrum of the first embodiment of the lithium-based solid electrolyte of the present invention. [Figure 6] FIG. 6 is a diagram showing a Raman spectrum of a general lithium tetraborate crystal. [Figure 7]FIG. 7 is a cross-sectional view illustrating a schematic diagram of an all-solid-state lithium ion secondary battery according to a preferred embodiment of the present invention. [Figure 8] FIG. 8 is a diagram showing an example of a reduced pair distribution function G(r) obtained by X-ray total scattering measurement of a specific lithium tetraborate described later. [Figure 9] FIG. 9 is a diagram showing an example of an X-ray total scattering profile of a specific lithium tetraborate. [Figure 10] FIG. 10 is a diagram showing an example of the structure factor S(Q) based on the X-ray total scattering profile obtained in FIG. [Figure 11] FIG. 11 is a diagram showing an example of an X-ray diffraction pattern for explaining requirement Y. [Figure 12] FIG. 12 shows the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement of the crystalline powder of Comparative Example 1. [Figure 13] FIG. 13 shows the X-ray diffraction pattern of the crystalline powder of Comparative Example 1. [Figure 14] FIG. 14 shows the X-ray diffraction pattern of the lithium-based solid electrolyte of Example 3. [Figure 15] FIG. 15 is an example of a Raman spectrum for explaining the requirement T. [Figure 16] FIG. 16 shows an example of the reduced pair distribution function G(r) obtained from an X-ray total scattering measurement of the fourth embodiment of the lithium-based solid electrolyte of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below. In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits.
[0011] The first and second embodiments of the lithium-based solid electrolyte of the present invention are characterized in that they contain a predetermined amount of various elements. In particular, the content of O (oxygen element) is relatively high, and the specific element A and the specific element B are contained in a predetermined amount. It is considered that O exists as water or an OH group in addition to BO3 or BO4 in the lithium-based solid electrolyte, and it is presumed that a hydration layer with good ion conductivity is formed on the surface side of the lithium-based solid electrolyte due to the high content of O. In addition, such a lithium-based solid electrolyte has excellent binding properties, which is also presumed to contribute to the improvement of ion conductivity. In addition, a feature of an example of the third embodiment of the lithium-based solid electrolyte of the present invention is that the mechanically milled lithium tetraborate is mixed with a predetermined component (water, lithium salt). As described later, the mechanically milled lithium tetraborate has a short-range ordered structure related to the atomic distances of BO and BB, but has almost no long-range ordered structure. The atomic distance of BO represents the distance between B and O that are chemically bonded, and the atomic distance of BB represents the distance between B and B that are close to each other. It is presumed that when such lithium tetraborate is used in combination with a predetermined component, a soft hydration layer is easily formed on the surface of the lithium tetraborate, and a large amount of lithium derived from the lithium salt is contained in this hydration layer, resulting in good ion conductivity. In addition, another feature of the third embodiment is that the amorphous lithium tetraborate is mixed with a predetermined component (water, lithium salt). It is presumed that when amorphous lithium tetraborate is used in combination with a specified component, a soft hydration layer is likely to form on the surface of the lithium tetraborate, and this hydration layer contains a large amount of lithium derived from the lithium salt, resulting in good ionic conductivity. The lithium-based solid electrolyte according to the fourth embodiment of the present invention is characterized by the following requirements X to Z. Requirement X mainly indicates that the lithium-based solid electrolyte has a short-range ordered structure, and requirement Y mainly indicates that the lithium-based solid electrolyte has almost no crystal structure and is amorphous. Requirement Z indicates that the lithium-based solid electrolyte contains many OH groups and a large amount of water. From these results, it is presumed that a soft hydration layer is formed on the surface side of the lithium-based solid electrolyte, and the presence of this hydration layer improves the ionic conductivity. Furthermore, as a feature of the fifth embodiment of the lithium-based solid electrolyte of the present invention, LiB3O5, Li3B 11 O 18 or Li3BO 12 The main features of this method are that it uses a mixture of LiB3O5 and Li3B 11 O 18 or Li3BO 12 When used in combination with certain ingredients, LiB3O5, Li3B 11 O 18 or Li3BO 12 It is presumed that a soft hydration layer is easily formed on the surface of the carbon nanotube, and this hydration layer contains a large amount of lithium derived from the lithium salt, resulting in good ionic conductivity. Moreover, the inorganic solid electrolyte of the present invention exhibits desired effects by satisfying the configuration described below. Each embodiment of the lithium-based solid electrolyte and the inorganic solid electrolyte of the present invention will be described in detail below.
[0012] <<First embodiment>> A first embodiment of the lithium-based solid electrolyte of the present invention will now be described.
[0013] <Lithium-based solid electrolyte> A first embodiment of the lithium-based solid electrolyte of the present invention contains Li (lithium element), B (boron element), and O (oxygen element). In addition, the first embodiment of the lithium-based solid electrolyte of the present invention further includes two or more specific elements selected from the group consisting of F (fluorine element), Cl (chlorine element), Br (bromine element), I (iodine element), S (sulfur element), P (phosphorus element), Si (silicon element), Se (selenium element), Te (tellurium element), C (carbon element), Sb (antimony element), As (arsenic element), Sc (scandium element), Y (yttrium element), Zr (zirconium element), Ti (titanium element), Hf (hafnium element), H (hydrogen element), and N (nitrogen element). The type of specific element included in the first embodiment of the lithium-based solid electrolyte of the present invention may be three or more. Among them, in terms of better ion conductivity (hereinafter also simply referred to as "the effect of the present invention is better"), the type of specific element included in the lithium-based solid electrolyte is preferably 2 to 5 types, more preferably 2 to 4 types. The first embodiment of the lithium-based solid electrolyte of the present invention preferably contains two or more specific elements selected from the group consisting of F, S, N, P, and C, more preferably contains two or more specific elements selected from the group consisting of F, S, C, and N, and even more preferably contains three specific elements of F, S, and N.
[0014] In a first embodiment of the lithium-based solid electrolyte of the present invention, the molar ratio of B to Li (B / Li) is more than 1.50 and less than 2.43. That is, in a first embodiment of the lithium-based solid electrolyte of the present invention, the relative value of the molar amount of B when the molar amount of Li is taken as 1.0 is more than 1.50 and less than 2.43. Among these, in terms of obtaining superior effects of the present invention, a suitable embodiment of the molar ratio of B to Li is preferably 1.70 to 2.30, and more preferably 1.90 to 2.10.
[0015] In a first embodiment of the lithium-based solid electrolyte of the present invention, the molar ratio of O to Li (O / Li) is greater than 2.34 and less than 6.86. That is, in a first embodiment of the lithium-based solid electrolyte of the present invention, the relative value of the molar amount of O when the molar amount of Li is taken as 1.0 is greater than 2.34 and less than 6.86. Among these, in terms of obtaining superior effects of the present invention, a suitable embodiment of the molar ratio of O to Li is preferably 3.00 to 6.50, more preferably 3.50 to 6.00, further preferably 4.50 to 6.00, and particularly preferably 5.00 to 6.00.
[0016] In the first embodiment of the lithium-based solid electrolyte of the present invention, the molar ratio of each specific element to Li (specific element / Li) is more than 0.001 and less than 0.17. That is, in the first embodiment of the lithium-based solid electrolyte of the present invention, the relative value of the molar content of each specific element when the molar content of Li is 1.0 is more than 0.001 and less than 0.17. As described above, in the first embodiment of the lithium-based solid electrolyte of the present invention, two or more specific elements are included. Therefore, for example, when the first embodiment of the lithium-based solid electrolyte of the present invention includes two specific elements, a specific element A and a specific element B that is a different type of element from the specific element A, the molar ratio of the specific element A to Li and the molar ratio of the specific element B to Li are each more than 0.001 and less than 0.17. Also, for example, when the first embodiment of the lithium-based solid electrolyte of the present invention includes three specific elements, a specific element A, a specific element B that is a different type of element from the specific element A, and a specific element C that is a different type of element from the specific elements A and B, the molar ratio of the specific element A to Li, the molar ratio of the specific element B to Li, and the molar ratio of the specific element C to Li are each more than 0.001 and less than 0.17. Among these, in terms of obtaining superior effects of the present invention, the molar ratio of each specific element to Li is preferably 0.003 to 0.15, and more preferably 0.01 to 0.14.
[0017] The contents of Li, B, and the specific element in the first embodiment of the lithium-based solid electrolyte of the present invention are determined by known elemental analysis. As an elemental analysis method, for example, Li and B are analyzed by ICP-OES (inductively coupled plasma optical emission spectrometry), N, which is one of the specific elements, is analyzed by an inert gas fusion method, and F and S, which are one of the specific elements, are analyzed by combustion ion chromatography. O can be calculated by adding up the analyzed masses of elements other than O and calculating the difference from the total amount of powder. The calculation method of the content of each element is not limited to the above, and for example, the content of one element may be estimated from the analysis result of the content of another element, taking into account the structure of the compound used. From the contents of the respective elements calculated by elemental analysis, the molar ratio of B to the above Li, the molar ratio of O to the above Li, and the molar ratio of each specific element to the above Li are calculated.
[0018] One preferred embodiment of the composition of the first embodiment of the lithium-based solid electrolyte of the present invention is a lithium-based solid electrolyte containing Li, B, O, F, S, and N, in which the molar ratio of B to Li is more than 1.50 and less than 2.43, the molar ratio of O to Li is more than 2.34 and less than 6.86, the molar ratio of F to Li is more than 0.001 and less than 0.17, the molar ratio of S to Li is more than 0.001 and less than 0.17, and the molar ratio of N to Li is more than 0.001 and less than 0.17. The preferred range of the molar ratio is as described above.
[0019] The first embodiment of the lithium-based solid electrolyte of the present invention may contain elements other than Li, B, O, and the specific element.
[0020] The manufacturing method of the first embodiment of the lithium-based solid electrolyte of the present invention will be described in detail later, but the lithium-based solid electrolyte of the present invention is preferably manufactured by a manufacturing method involving mechanical milling. For example, it is presumed that by performing mechanical milling on the raw material of the first embodiment of the lithium-based solid electrolyte of the present invention (e.g., lithium-based oxide containing Li and B), the crystalline component in the raw material can be made amorphous, and as a result, it becomes easier to form a hydration layer with excellent ion conductivity.
[0021] In addition, the solid electrolyte of the first embodiment of the lithium-based solid electrolyte of the present invention has a better effect than the solid electrolyte of the first embodiment of the present invention. 7 The solid of the first embodiment of the lithium-based solid electrolyte of the present invention is a solid of the first embodiment of the lithium-based solid electrolyte of the present invention, with respect to the full width at half maximum of the peak appearing in the chemical shift range of -100 to +100 ppm in the spectrum obtained when Li-NMR measurement is performed at 20 ° C. 7 The ratio of the full width at half maximum of the peak appearing in the chemical shift range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement at 120°C is preferably 50% or less, more preferably 40% or less, and even more preferably 35% or less. There is no particular lower limit, but it is often 10% or more. The full width at half maximum (FWHM) of a peak refers to the width (ppm) at half the height (H) of the peak (H / 2).
[0022] The above characteristics will be explained below with reference to FIG. FIG. 1 shows a solid electrolyte according to a first embodiment of the lithium-based solid electrolyte of the present invention. 7 An example of the spectrum obtained when Li-NMR measurement was performed at 20°C or 120°C is shown below. The solid line spectrum shown at the bottom of Fig. 1 is 7 The spectrum obtained when Li-NMR measurement was performed at 20°C. The spectrum shown at the top of Figure 1 is the solid 7 This is the spectrum obtained when Li-NMR measurement was performed at 120°C. Generally, solid 7 In Li-NMR measurements, Li +When the mobility of Li is high, the peak obtained is sharper. In the embodiment shown in FIG. 1, the spectrum at 120° C. is sharper than the spectrum at 20° C. In other words, in the lithium-based solid electrolyte shown in FIG. + This indicates that the mobility of Li is high. Such lithium-based solid electrolytes are prone to plastic deformation due to their amorphous structure, and Li + It is believed that the effects of the present invention are more excellent due to the excellent hopping property of the compound. For example, regarding lithium tetraborate crystals, 7 When Li-NMR measurements are performed at 20°C or 120°C, the spectrum measured at 20°C, represented by the solid line in the lower part of Figure 2, and the spectrum measured at 120°C, represented by the dashed line in the upper part of Figure 2, tend to have approximately the same shape.
[0023] The above solid 7 The Li-NMR measurement conditions are as follows. Specifically, a 4 mm HX CP-MAS probe is used, and measurements are performed using the single pulse method, 90° pulse width: 3.2 μs, observation frequency: 155.546 MHz, observation width: 1397.6 ppm, repetition time: 15 sec, accumulation: 1 time, and MAS rotation speed: 0 Hz.
[0024] In addition, the solid electrolyte of the first embodiment of the lithium-based solid electrolyte of the present invention has a superior effect. 7 When a spectrum obtained by Li-NMR measurement at 20°C is subjected to waveform separation of a first peak appearing in the range of -100 to +100 ppm, it is preferable that a second peak with a chemical shift in the range of -3 to 3 ppm and a full width at half maximum of 5 ppm or less is present, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more. The ratio of the area intensity is more preferably 2% or more, and further preferably 15% or more. There is no particular upper limit to the ratio of the area intensity, but it is often 50% or less.
[0025] The above characteristics will be explained below with reference to FIGS. FIG. 3 shows a solid electrolyte according to a first embodiment of the lithium-based solid electrolyte of the present invention. 7 An example of a spectrum obtained when Li-NMR measurement was performed at 20° C. is shown in FIG. 3. As shown in FIG. 3, in the first embodiment of the lithium-based solid electrolyte of the present invention, a peak (corresponding to the first peak) is observed in the range of −100 to +100 ppm, and in this first peak, a small peak is observed near the chemical shift of 0 ppm as surrounded by a dashed line. As described above, Li + When the mobility of the protein is high, the peak is observed sharply, which is thought to be the influence of the high mobility. Next, the waveform separation of the first peak is shown in Figure 4. As shown in Figure 4, the first peak is separated into a small peak (corresponding to the second peak) represented by a solid line and a large peak represented by a dashed line. The second peak appears in the chemical shift range of -3 to 3 ppm and has a full width at half maximum of 5 ppm or less. In the first embodiment of the lithium-based solid electrolyte of the present invention, the ratio of the area intensity of the second peak represented by the solid line in FIG. 4 to the area intensity of the first peak (peak before waveform separation) represented by FIG. 3 {(area intensity of the second peak / area intensity of the first peak)×100} is within the above range. Methods for waveform separation include methods using known software, such as graph processing software Igor Pro from WaveMetrics.
[0026] In addition, in terms of the superior effect of the present invention, in the infrared absorption spectrum of the first embodiment of the lithium-based solid electrolyte of the present invention, -1 The maximum absorption intensity in the wavenumber region of 3000 to 3500 cm -1 The ratio of the maximum absorption intensity in the wave number region of is preferably 1 / 5 or more. In particular, in terms of the superior effect of the present invention, the ratio is preferably 3 / 10 or more, and more preferably 2 / 5 or more. There is no particular upper limit, but it is preferably 1 or less. Infrared absorption spectrum 3000-3500 cm -1 The OH stretching vibration mode is observed in the wavenumber region of 800–1600 cm-1 In the wave number region, the BO stretching vibration mode is observed. In the first embodiment of the lithium-based solid electrolyte of the present invention, the absorption intensity derived from the OH stretching vibration mode is strongly observed, and it is understood that the first embodiment of the lithium-based solid electrolyte of the present invention contains a large number of OH groups and a large amount of water. In such a lithium-based solid electrolyte, it is considered that the lithium ions are easily moved, and as a result, the ion conductivity is improved. In addition, 800~1600cm -1 In the wavenumber region, vibrational modes originating from lithium salts can also be observed.
[0027] The conditions for measuring the infrared absorption spectrum are as follows. Specifically, objective lens: 32x Cassegrain type (NA 0.65), detector: MCT-A, measurement range: 650-4000 cm -1 , resolution: 4cm -1 , Sample cell: Measurement is performed using a diamond cell. The infrared absorption spectrum obtained is corrected to remove signals from atmospheric water and CO2, and an offset correction is applied to the background to set the absorption intensity to zero. In addition, when measuring the infrared absorption spectrum of the first embodiment of the lithium-based solid electrolyte of the present invention, the measurement is carried out in the atmosphere after vacuum drying at 40° C. for 2 hours.
[0028] In addition, the effect of the present invention is more excellent in that the first embodiment of the lithium-based solid electrolyte of the present invention has a Raman spectrum of 600 to 850 cm -1 The coefficient of determination obtained by performing linear regression analysis by the least squares method in the wave number region is preferably 0.9400 or more. In addition, the coefficient of determination is more preferably 0.9600 or more in terms of the effect of the present invention being more excellent. The upper limit is not particularly limited, but may be 1.0000.
[0029] The above will be explained below with reference to FIG. 5 shows an example of the Raman spectrum of the first embodiment of the lithium-based solid electrolyte of the present invention. The vertical axis shows the Raman intensity, and the horizontal axis shows the Raman shift from 600 to 850 cm -1 The coefficient of determination (R 2 ) is calculated. In other words, the 600-850 cm -1 In the wavenumber region, the regression line (thick dashed line in Figure 5) is calculated by the least squares method, and the coefficient of determination R 2 The coefficient of determination is calculated based on the linear correlation between the measurements, taking a value between 0 (no linear correlation) and 1 (perfect linear correlation between the measurements). In the first embodiment of the lithium-based solid electrolyte of the present invention, as shown in FIG. -1 Almost no peaks are observed in the wavenumber region, resulting in a high coefficient of determination. The above coefficient of determination R 2 corresponds to the square of the correlation coefficient (Pearson's product moment correlation coefficient). More specifically, in this specification, the coefficient of determination R 2 is calculated by the following formula, where x1 and y1 represent the wavenumber in the Raman spectrum and the Raman intensity corresponding to that wavenumber, x2 represents the (arithmetic) average of the wavenumbers, and y2 represents the (arithmetic) average of the Raman intensity.
[0030]
number
[0031] On the other hand, the Raman spectrum of a typical lithium tetraborate crystal is shown in Figure 6. As shown in Figure 6, the typical lithium tetraborate crystal has a peak at 716-726 cm due to its structure. -1 , and 771-785cm -1 A peak is observed in the wavenumber region. If such a peak exists, the peak at 600 to 850 cm -1 When linear regression analysis is performed by the least squares method in the wavenumber region to calculate the coefficient of determination, the coefficient of determination is less than 0.9400. In other words, the fact that the coefficient of determination is 0.9400 or more indicates that the first embodiment of the lithium-based solid electrolyte of the present invention contains almost no crystal structure contained in general lithium tetraborate crystals. Therefore, as a result, the first embodiment of the lithium-based solid electrolyte of the present invention contains Li + It is believed that the hopping property is excellent.
[0032] In order to obtain better effects of the present invention, it is preferable that the first embodiment of the lithium-based solid electrolyte of the present invention satisfies the following requirement T. Requirement T: In the Raman spectrum of lithium-based solid electrolytes, the peak intensity is 710 to 730 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The first peak above, 770-790 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The second peak above and 1020-1040 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 None of the above third peaks are present, or In the above Raman spectrum, when at least one specific peak selected from the group consisting of a first peak, a second peak, and a third peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: 400 to 600 cm of the above Raman spectrum -1 The point showing the minimum value M1 of the Raman intensity in the wavenumber region of 1300 to 1500 cm in the above Raman spectrum -1 A straight line is drawn by connecting the points showing the minimum value M2 of the Raman intensity in the wave number region of 710 to 730 cm in the region from the wave number showing the minimum value M1 to the wave number showing the minimum value M2. -1 , 770~790cm -1 , and 1020~1040cm -1An average difference value between the Raman intensity of the straight line and the Raman intensity of the Raman spectrum at each wavenumber in the region other than the region is calculated, and an absolute value of the difference between the Raman intensity of the peak at the wavenumber showing the peak top of the specific peak and the Raman intensity of the straight line is calculated, and the ratio of the absolute value of the difference to the average difference value is defined as the intensity ratio. The above requirement T will be explained below.
[0033] First, in the Raman spectrum of the lithium-based solid electrolyte, -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The first peak above, 770-790 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The second peak above and 1020-1040 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 If none of the above third peaks is present, requirement T is met. The full width at half maximum of a peak is the width (cm) at half the height of the peak. -1 )
[0034] Furthermore, when at least one specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present in the Raman spectrum of the lithium-based solid electrolyte, requirement T is also satisfied when the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. In particular, it is preferable that the above intensity ratio is satisfied for all of the specific peaks. The strength measurement method will be described below with reference to FIG. Fig. 15 is a diagram showing an example of the Raman spectrum of a lithium-based solid electrolyte, where the vertical axis is the Raman intensity and the horizontal axis is the Raman shift. In Fig. 15, for ease of explanation, an example in which one specific peak exists is shown. In the strength measurement method, first, the 400-600 cm region of the Raman spectrum of the lithium-based solid electrolyte is -1 The point showing the minimum value M1 of the Raman intensity in the wavenumber region of 1300 to 1500 cm in the above Raman spectrum -115, a straight line is obtained by connecting the point P1 indicating the minimum value M1 and the point P2 indicating the minimum value M2 of the Raman intensity in the wavenumber region of 100 nm to obtain a straight line. Specifically, as shown in FIG. 15, a straight line is obtained by connecting the point P1 indicating the minimum value M1 and the point P2 indicating the minimum value M2. Next, in the region from the wave number showing the minimum value M1 (W1 in FIG. 15) to the wave number showing the minimum value M2 (W2 in FIG. 15), -1 , 770~790cm -1 , and 1020~1040cm -1 The average difference value between the Raman intensity of the line and the Raman intensity of the Raman spectrum at each wave number in the region other than the region (hereinafter also referred to as the "specific region") is calculated. Note that the average difference value is the Raman intensity of the line in the 2 cm from W1 to W2 in the specific region. -1 The absolute value of the difference between the Raman intensity of the straight line and the Raman intensity of the Raman spectrum at each wave number is calculated, and the absolute values of the differences are averaged. Next, the absolute value of the difference between the Raman intensity of the specific peak at the wave number showing the peak top and the Raman intensity of the straight line is calculated, and the ratio of the absolute value of the difference to the average difference value is calculated as the intensity ratio. More specifically, as shown in Fig. 15, the absolute value (|S1-S2|) of the difference between the Raman intensity S1 of the peak at the wave number W3 showing the peak top and the Raman intensity S2 of the straight line at the wave number W3 is calculated, and it is checked whether the absolute value of the obtained difference is 5.0 times or less of the average difference value.
[0035] When the above requirement T is satisfied, this means that no or almost no crystal structure exists in the lithium-based solid electrolyte, and the electrolyte is in an amorphous state. That is, the first to third peaks described in requirement Y are mainly peaks derived from the crystal structure in the lithium-based solid electrolyte (particularly, the crystal structure of lithium tetraborate), and when these peaks are not present, the lithium-based solid electrolyte does not have a specific crystal structure and is in an amorphous state, so it is presumed that, as described above, a hydrated layer with excellent ion conductivity is easily formed. Even when at least one of the first to third peaks is present, the intensity ratio of any one of the specific peaks present is equal to or less than a predetermined value, which indicates that the lithium-based solid electrolyte has almost no crystal structure, and it is presumed that, as described above, a hydrated layer with excellent ion conductivity is easily formed. In addition, in the lithium-based solid electrolyte, a peak due to other factors may occur in addition to the peak derived from a specific crystal structure such as the crystal structure of lithium tetraborate given as an example. Examples of other factors include peaks derived from impurities, and such peaks may overlap with the first to third peaks described above. When an amorphous state is achieved that is presumed to be capable of forming a hydration layer with excellent ion conductivity, all of the first to third peaks are often reduced. Even if, as described above, a peak due to another factor happens to overlap with any of the first to third peaks to produce a large peak, the presence of a specific peak whose intensity ratio is equal to or less than a predetermined value indicates that the lithium-based solid electrolyte is in an amorphous state that is presumed to be capable of forming a hydration layer with excellent ion conductivity.
[0036] In the Raman spectrum of the lithium-based solid electrolyte, when the first peak, the second peak, and the third peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. In particular, when the first peak, the second peak, and the third peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less, and it is particularly preferable that the first peak, the second peak, and the third peak are not present.
[0037] The Raman spectrum is measured by Raman imaging. Raman imaging is a microspectroscopic technique that combines Raman spectroscopy with microscopy. Specifically, it is a technique in which excitation light is scanned over a sample to detect measurement light that contains Raman scattered light, and the distribution of components is visualized based on the intensity of the measurement light. The measurement conditions for Raman imaging are as follows: 27°C, atmospheric air, excitation light of 532 nm, objective lens of 100x, mapping method point scanning, 1 μm step, exposure time per point of 1 second, number of integrations of 1, and measurement range of 70 μm x 50 μm. However, the measurement range may be narrower depending on the film thickness of the sample. In addition, the Raman spectrum data is subjected to a principal component analysis (PCA) process to remove noise. Specifically, in the PCA process, the spectra are recombined using components with an autocorrelation coefficient of 0.6 or more.
[0038] In order to obtain a more excellent effect of the present invention, the mass loss rate of the first embodiment of the lithium-based solid electrolyte of the present invention when heated to 800° C. is preferably 20 to 40% by mass. In particular, in order to obtain a more excellent effect of the present invention, the mass loss rate is more preferably 25 to 35% by mass. The mass reduction of the first embodiment of the lithium-based solid electrolyte of the present invention that occurs during the heating is believed to be due to the removal of moisture contained in the lithium-based solid electrolyte. The fact that the mass reduction rate is a predetermined amount as described above indicates that the lithium-based solid electrolyte contains a predetermined amount of moisture, and it is believed that the presence of such moisture improves the conductivity of lithium ions. When the heat treatment is carried out, the material is heated at a temperature increase rate of 20° C. / sec in the range of 25° C. to 800° C. For the measurement, a known thermogravimetric differential thermal analyzer (TG-DTA) can be used. The mass reduction rate is calculated by {(mass at 25° C.−mass at 800° C.) / mass at 25° C.}×100. In order to carry out the above heat treatment, the first embodiment of the lithium-based solid electrolyte of the present invention is vacuum-dried at 40° C. for 2 hours, and then the measurement is carried out in the atmosphere.
[0039] The bulk modulus of the first embodiment of the lithium-based solid electrolyte of the present invention is not particularly limited, but is preferably 45 GPa or less, more preferably 40 GPa or less, in terms of the superior effect of the present invention. The lower limit is not particularly limited, but is preferably 5 GPa or more. The bulk modulus is measured by an ultrasonic attenuation method. Specifically, first, a suspension is prepared by suspending the first embodiment of the lithium-based solid electrolyte of the present invention in pure water. The content of the first embodiment of the lithium-based solid electrolyte of the present invention in the suspension is 1.2% by mass with respect to the total mass of the suspension. Next, the ultrasonic attenuation spectrum of the suspension is measured, and the bulk modulus of the first embodiment of the lithium-based solid electrolyte of the present invention is obtained by fitting according to the scattering attenuation theory formula. When performing the fitting, the particle size distribution, density (2.3 g / ml), and Poisson's ratio (0.12) of the lithium-based solid electrolyte of the present invention are used. Regarding fitting using the above scattering attenuation theory, the bulk modulus is calculated using equations (7), (12), and (13) described in Kohjiro Kubo et al., Ultrasonics 62 (2015) 186-194. In addition, the particle size distribution of the first embodiment of the lithium-based solid electrolyte of the present invention is obtained by acquiring particle images by a flow particle image analysis method, and obtaining a histogram (particle size distribution) of the particle size of the first embodiment of the lithium-based solid electrolyte of the present invention. The particle size corresponds to the circle equivalent diameter.
[0040] The median diameter (D50) of the first embodiment of the lithium-based solid electrolyte of the present invention is not particularly limited, but is preferably 0.01 to 20 μm, more preferably 0.1 to 2.0 μm, in terms of better effects of the present invention. The median diameter (D50) was measured by obtaining particle images by flow particle image analysis, calculating the particle diameter distribution of the first embodiment of the lithium-based solid electrolyte of the present invention, and analyzing the obtained distribution. The particle diameter corresponds to the circle equivalent diameter.
[0041] <<Second embodiment>> A second embodiment of the lithium-based solid electrolyte of the present invention comprises Li, B, and O. The second embodiment of the lithium-based solid electrolyte of the present invention further includes two or more specific elements selected from the group consisting of Group 4 elements of the periodic table, Group 15 elements of the periodic table, Group 16 elements of the periodic table, Group 17 elements of the periodic table, Si, C, Sc, Y, and H. In terms of better effects of the present invention, the second embodiment of the lithium-based solid electrolyte of the present invention preferably includes two or more specific elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N. Group 4 elements of the periodic table include Ti, Zr, Hr, and Rf. Group 15 elements of the periodic table include N, P, As, Sb, Bi, and Mc. Group 16 elements of the periodic table include O, S, Se, Te, Po, and Lv. Group 17 elements of the periodic table include F, Cl, Br, I, At, and Ts. The number of types of specific elements included in the second embodiment of the lithium-based solid electrolyte of the present invention may be three or more. Among them, in terms of more excellent effects of the present invention, the number of types of specific elements included in the lithium-based solid electrolyte is preferably 2 to 5 types, and more preferably 2 to 4 types. The second embodiment of the lithium-based solid electrolyte of the present invention preferably includes two or more specific elements selected from the group consisting of F, S, N, P, and C, more preferably includes two or more specific elements selected from the group consisting of F, S, C, and N, and even more preferably includes three specific elements of F, S, and N.
[0042] As described later, when manufacturing the second embodiment of the lithium-based solid electrolyte of the present invention, it is preferable to use lithium tetraborate as a raw material. At this time, the lithium tetraborate used is usually a compound represented by Li2B4O7 and is mainly a compound composed of Li, B, and O, but in the present invention, it may deviate from the above standard values. More specifically, as the lithium tetraborate, a compound represented by Li 2+x B 4+y O 7+z (-0.3 < x < 0.3, -0.3 < y < 0.3, -0.3 < z < 0.3) is preferable. That is, when the molar amount of B is 4.00 and the molar amount of Li is represented, the molar amount of Li is preferably 1.58 to 2.49, and the molar amount of O is preferably 6.23 to 7.89. In other words, when the contained molar amount of B is 4.00, the relative value of the contained molar amount of Li is 1.58 to 2.49, and the molar amount of O is preferably 6.23 to 7.89.
[0043] In the second embodiment of the lithium-based solid electrolyte of the present invention, when the molar amount of B in the lithium-based solid electrolyte is 4.00 and the molar amount of Li is represented, the molar amount of Li is 1.58 to 3.49. That is, when the contained molar amount of B is 4.00, the relative value of the contained molar amount of Li is 1.58 to 3.49. In particular, in terms of superior effects of the present invention, when the molar amount of B in the lithium-based solid electrolyte is taken as 4.00 and the molar amount of Li is expressed, the molar amount of Li is preferably 1.58 to 3.00, more preferably 1.90 to 3.00, and even more preferably 2.00 to 3.00.
[0044] In a second embodiment of the lithium-based solid electrolyte of the present invention, when the molar amount of B in the lithium-based solid electrolyte is 4.00 and the molar amount of O is expressed, the molar amount of O is 6.23 to 25.00. In other words, when the molar amount of B contained is 4.00, the relative value of the molar amount of O contained is 6.23 to 25.00. Among these, in terms of superior effects of the present invention, when the molar amount of B in the lithium-based solid electrolyte is taken as 4.00 and the molar amount of O is expressed, the molar amount of O is preferably 10.00 to 23.00.
[0045] In the second embodiment of the lithium-based solid electrolyte of the present invention, when the molar amount of B in the lithium-based solid electrolyte is 4.00 and the molar amount of each specific element is expressed, the molar amount of each specific element is 0.001 to 10.00. In other words, when the molar amount of B contained is 4.00, the relative value of the molar amount of each specific element contained is 0.001 to 10.00. In particular, in terms of superior effects of the present invention, when the molar amount of B in the lithium-based solid electrolyte is taken as 4.00 and the molar amount of each specific element is expressed, the molar amount of each specific element is preferably 0.001 to 6.0, and more preferably 0.01 to 5.0. As described above, the second embodiment of the lithium-based solid electrolyte of the present invention contains two or more specific elements. Therefore, for example, when the second embodiment of the lithium-based solid electrolyte of the present invention contains two specific elements, a specific element A and a specific element B which is a different type of element from the specific element A, when the molar amount of B in the lithium-based solid electrolyte is 4.00, the molar amount of the specific element A and the molar amount of the specific element B are each 0.001 to 10.00. Also, for example, when the second embodiment of the lithium-based solid electrolyte of the present invention contains three specific elements, a specific element A, a specific element B which is a different type of element from the specific element A, and a specific element C which is a different type of element from the specific elements A and B, when the molar amount of B in the lithium-based solid electrolyte is 4.00, the molar amount of the specific element A, the molar amount of the specific element B, and the molar amount of the specific element C are each 0.001 to 10.00.
[0046] The contents of Li, B, and the specific element in the second embodiment of the lithium-based solid electrolyte of the present invention are determined by known elemental analysis. As an elemental analysis method, for example, Li and B are analyzed by ICP-OES (Inductively Coupled Plasma Optical Emission Spectrometry), N, which is one of the specific elements, is analyzed by an inert gas fusion method, and F and S, which are one of the specific elements, are analyzed by combustion ion chromatography. O can be calculated by adding up the analyzed masses of elements other than O and calculating the difference from the total amount of powder. Note that the calculation method of the content of each element is not limited to the above, and the content of one element may be estimated from the analysis result of the content of another element, taking into account the structure of the compound used. From the contents of the respective elements calculated by elemental analysis, the molar amounts of Li, O, and the specific element are calculated when the molar amount of B is set to 4.00.
[0047] One preferred embodiment of the composition of the second embodiment of the lithium-based solid electrolyte of the present invention includes a lithium-based solid electrolyte containing Li, B, O, F, S, and N, in which, when the molar amount of B is 4.00, the molar amount of Li is 1.58 to 3.49 (preferably, 1.58 to 3.00), the molar amount of O is 6.23 to 25.00, the molar amount of F is 0.001 to 10.00, the molar amount of S is 0.001 to 2.00, and the molar amount of N is 0.001 to 1.00. The preferred range of the molar ratio is as described above.
[0048] The second embodiment of the lithium-based solid electrolyte of the present invention may contain elements other than Li, B, O, and the specific element.
[0049] The manufacturing method of the second embodiment of the lithium-based solid electrolyte of the present invention will be described in detail later, but the lithium-based solid electrolyte of the present invention is preferably manufactured by a manufacturing method involving mechanical milling. For example, it is presumed that by performing mechanical milling on the raw material of the second embodiment of the lithium-based solid electrolyte of the present invention (e.g., lithium-based oxide containing Li and B), the crystalline component in the raw material can be made amorphous, and as a result, it becomes easier to form a hydration layer with excellent ion conductivity.
[0050] In addition, the solid electrolyte of the second embodiment of the lithium-based solid electrolyte of the present invention is more excellent in the effect of the present invention. 7 The solid of the second embodiment of the lithium-based solid electrolyte of the present invention is a solid of the second embodiment of the lithium-based solid electrolyte of the present invention, with respect to the full width at half maximum of the peak appearing in the chemical shift range of -100 to +100 ppm in the spectrum obtained when Li-NMR measurement is performed at 20 ° C. 7 The ratio of the full width at half maximum of the peak appearing in the chemical shift range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement at 120°C is preferably 50% or less, more preferably 40% or less, and even more preferably 35% or less. There is no particular lower limit, but it is often 10% or more. The full width at half maximum (FWHM) of a peak refers to the width (ppm) at half the height (H) of the peak (H / 2). The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0051] In addition, the solid electrolyte of the second embodiment of the lithium-based solid electrolyte of the present invention is more excellent in the effect of the present invention. 7 When a spectrum obtained by Li-NMR measurement at 20°C is subjected to waveform separation of a first peak appearing in the range of -100 to +100 ppm, it is preferable that a second peak with a chemical shift in the range of -3 to 3 ppm and a full width at half maximum of 5 ppm or less is present, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more. The ratio of the area intensity is more preferably 2% or more, and further preferably 15% or more. There is no particular upper limit to the ratio of the area intensity, but it is often 50% or less. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0052] In addition, in terms of the superior effect of the present invention, in the infrared absorption spectrum of the second embodiment of the lithium-based solid electrolyte of the present invention, -1 The maximum absorption intensity in the wavenumber region of 3000 to 3500 cm -1 The ratio of the maximum absorption intensity in the wave number region of is preferably 1 / 5 or more. In particular, in terms of the superior effect of the present invention, the ratio is preferably 3 / 10 or more, and more preferably 2 / 5 or more. There is no particular upper limit, but it is preferably 1 or less. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0053] In addition, the effect of the present invention is more excellent in that the range of 600 to 850 cm in the Raman spectrum of the second embodiment of the lithium-based solid electrolyte of the present invention is -1 The coefficient of determination obtained by performing linear regression analysis by the least squares method in the wave number region is preferably 0.9400 or more. In addition, the coefficient of determination is more preferably 0.9600 or more in terms of the effect of the present invention being more excellent. The upper limit is not particularly limited, but may be 1.0000. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment. In addition, in terms of obtaining better effects of the present invention, it is preferable that the second embodiment of the lithium-based solid electrolyte of the present invention satisfies requirement T. The following requirement T is the same as the requirement T defined in the above-mentioned first embodiment, and the measurement method thereof is also as explained in the first embodiment. Requirement T: In the Raman spectrum of lithium-based solid electrolytes, the peak intensity is 710 to 730 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The first peak above, 770-790 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The second peak above and 1020-1040 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 None of the above third peaks are present, or In the above Raman spectrum, when at least one specific peak selected from the group consisting of a first peak, a second peak, and a third peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: 400 to 600 cm of the above Raman spectrum -1 The point showing the minimum value M1 of the Raman intensity in the wavenumber region of 1300 to 1500 cm in the above Raman spectrum -1 A straight line is drawn by connecting the points showing the minimum value M2 of the Raman intensity in the wave number region of 710 to 730 cm in the region from the wave number showing the minimum value M1 to the wave number showing the minimum value M2. -1 , 770~790cm -1 , and 1020~1040cm -1 An average difference value between the Raman intensity of the straight line and the Raman intensity of the Raman spectrum at each wavenumber in the region other than the region is calculated, and an absolute value of the difference between the Raman intensity of the peak at the wavenumber showing the peak top of the specific peak and the Raman intensity of the straight line is calculated, and the ratio of the absolute value of the difference to the average difference value is defined as the intensity ratio.
[0054] In the Raman spectrum of the lithium-based solid electrolyte, when the first peak, the second peak, and the third peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. In particular, when the first peak, the second peak, and the third peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less, and it is particularly preferable that the first peak, the second peak, and the third peak are not present.
[0055] In order to obtain a more excellent effect of the present invention, the mass loss rate of the second embodiment of the lithium-based solid electrolyte of the present invention when heated to 800° C. is preferably 20 to 40% by mass. In particular, in order to obtain a more excellent effect of the present invention, the mass loss rate is more preferably 25 to 35% by mass. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0056] The bulk modulus of the second embodiment of the lithium-based solid electrolyte of the present invention is not particularly limited, but is preferably 45 GPa or less, more preferably 40 GPa or less, in terms of the superior effect of the present invention. The lower limit is not particularly limited, but is preferably 5 GPa or more. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0057] The median diameter (D50) of the second embodiment of the lithium-based solid electrolyte of the present invention is not particularly limited, but is preferably 0.01 to 20 μm, more preferably 0.1 to 2.0 μm, in terms of better effects of the present invention. The median diameter (D50) was measured by obtaining particle images by flow particle image analysis, calculating the particle diameter distribution of the second embodiment of the lithium-based solid electrolyte of the present invention, and analyzing the obtained distribution. The particle diameter corresponds to the circle equivalent diameter.
[0058] In order to obtain a more excellent effect of the present invention, the second embodiment of the lithium-based solid electrolyte of the present invention preferably satisfies the following requirement X. The following requirement X is the same as the requirement X defined in the fourth embodiment described later, and will be described in detail later. Requirement X: In the reduced pair distribution function G(r) obtained from X-ray total scattering measurement of the lithium-based solid electrolyte, there is a first peak whose peak top is located in an r range of 1.43±0.2 Å and a second peak whose peak top is located in an r range of 2.40±0.2 Å, and the G(r) at the peak top of the first peak is greater than 1.0 (preferably 1.2 or greater), and the G(r) at the peak top of the second peak is 0.8 or greater (preferably greater than 1.0).
[0059] In order to obtain a more excellent effect of the present invention, the second embodiment of the lithium-based solid electrolyte of the present invention preferably satisfies the following requirement Y. The following requirement Y is the same as the requirement Y defined in the fourth embodiment described later, and will be described in detail later. Requirement Y: In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of a lithium-based solid electrolyte, none of the following peaks are present: a first peak having a peak top in the range of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, a second peak having a peak top in the range of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, a third peak having a peak top in the range of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and a fourth peak having a peak top in the range of 34.4 to 34.8° and a full width at half maximum of 0.65° or less; or In the X-ray diffraction pattern, when at least one specific peak selected from the group consisting of a first peak, a second peak, a third peak, and a fourth peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: Calculate average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of a specific peak, calculate average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of a specific peak, calculate the arithmetic average of average intensity 1 and average intensity 2, and the ratio of the peak intensity at the peak top of the specific peak to the arithmetic average is the intensity ratio.
[0060] In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of the second embodiment of the lithium-based solid electrolyte, if none of the first peak, the second peak, the third peak, and the fourth peak is present, or if a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. Among them, if none of the first peak, the second peak, the third peak, and the fourth peak is present, or if a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less.
[0061] <<Third embodiment>> A third embodiment of the lithium-based solid electrolyte of the present invention comprises mechanically milled lithium tetraborate, water, and a lithium salt. Each component will be described in detail below.
[0062] (Mechanically milled lithium tetraborate (hereinafter referred to as "specific lithium tetraborate")) The lithium tetraborate contained in the third embodiment of the lithium-based solid electrolyte of the present invention is subjected to mechanical milling treatment. First, the lithium tetraborate included in the third embodiment is usually a compound represented by Li2B4O7, which is a compound mainly composed of Li, B and O, but in the present invention, it may deviate from the above standard value. More specifically, the lithium tetraborate is Li 2+x B 4+y O 7+zA compound represented by (-0.3 < x < 0.3, -0.3 < y < 0.3, -0.3 < z < 0.3) is preferred.
[0063] Examples of the mechanical milling treatment performed on lithium tetraborate include the mechanical milling treatment performed in Step 1A described later, and the details will be described in detail later. By performing a mechanical milling treatment on lithium tetraborate, it is presumed that lithium tetraborate can be amorphized, and as a result, it becomes easier to form a hydration layer with excellent ionic conductivity.
[0064] Specific lithium tetraborate preferably satisfies the following requirement W in that the effects of the present invention are more excellent. That is, specific lithium tetraborate is preferably lithium tetraborate exhibiting the characteristics indicated by requirement W. Requirement W: In the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement of specific lithium tetraborate, there are a first peak whose peak top is located in the range of r = 1.43 ± 0.2 Å and a second peak whose peak top is located in the range of r = 2.40 ± 0.2 Å, G(r) at the peak top of the first peak and G(r) at the peak top of the second peak are greater than 1.0, and the absolute value of G(r) is less than 1.0 in the range where r is greater than 5 Å and less than or equal to 10 Å. Hereinafter, requirement W will be described with reference to FIGS. 8 to 10.
[0065] FIG. 8 shows an example of the reduced pair distribution function G(r) obtained by X-ray total scattering measurement of specific lithium tetraborate. The vertical axis in FIG. 8 is the reduced pair distribution function obtained by Fourier-transforming the X-ray scattering, and indicates the probability that an atom exists at the position of the distance r. The X-ray total scattering measurement is performed at SPring-8 BL04B2 (acceleration voltage 61.4 keV, wavelength 0.2019 Å). The reduced pair distribution function G(r) is obtained by converting the scattering intensity I obtained by the experiment according to the following procedure. First, the scattering intensity I obs is represented by Equation (1). Also, the structure factor S(Q) is I cohis obtained by dividing by the product of the number of atoms N and the atomic scattering factor f. I obs =I coh +I incoh +I 蛍光 (1)
[0066]
number
[0067] The structure factor S(Q) must be used for PDF (Pair Distribution Function) analysis. In the above formula (2), the required intensity is the coherent scattering I coh Incoherent Scattering I incoh and X-ray fluorescence I 蛍光 is the scattering intensity I obtained by blank measurement, subtraction using the theoretical formula, and discriminator of the detector. obs An example of the total scattering measurement result of a specific lithium tetraborate and the extracted structure factor S(Q) are shown in Figures 9 and 10. Coherent scattering is expressed by Debye's scattering formula (3) (N: total number of atoms, f: atomic scattering factor, r ij :ij interatomic distance).
[0068]
number
[0069] If we focus on an arbitrary atom and the atomic density at a distance r is ρ(r), then the number of atoms present within a sphere of radius r-r+d(r) is 4πr 2 Since ρ(r)dr, equation (3) can be expressed as equation (4).
[0070]
number
[0071] By taking the average density of atoms as ρ0 and rearranging equation (4), we obtain equation (5).
[0072]
number
[0073] Equation (6) is obtained from equation (5) and equation (2).
[0074]
number
[0075] The pair distribution function g(r) is expressed by equation (7).
[0076]
number
[0077] From the above equations (6) and (7), equation (8) is obtained.
[0078]
number
[0079] As described above, the pair distribution function can be obtained by the Fourier transform of the structure factor S(Q). In order to make it easier to observe the medium- and long-range order, the pair distribution function is converted to G(r) = 4πr(g(r)-1) to obtain the reduced pair distribution function (Figure 8). g(r), which oscillates around 0, represents the density difference from the average density at each interatomic distance, and if there is a correlation at a specific interatomic distance, the average density will be higher than 1. Therefore, it reflects the distance and coordination number of elements corresponding to the local to medium distance. When order is lost, ρ(r) approaches the average density, and g(r) approaches 1. Therefore, in an amorphous structure, the larger r is, the less order there is, so g(r) becomes 1, i.e., G(r) becomes 0.
[0080] In requirement W, as shown in FIG. 8, in the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement, there is a first peak P1 whose peak top is located in the r range of 1.43±0.2 Å and a second peak P2 whose peak top is located in the r range of 2.40±0.2 Å, and G(r) at the peak top of the first peak P1 and G(r) at the peak top of the second peak P2 exceed 1.0. That is, in the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement of the specific lithium tetraborate, a first peak is observed in which the G(r) of the peak top (hereinafter also referred to as the "first peak top") exceeds 1.0 and the first peak top is located in the range of 1.43±0.2 Å, and a second peak is observed in which the G(r) of the peak top (hereinafter also referred to as the "second peak top") exceeds 1.0 and the second peak top is located in the range of 2.40±0.2 Å. In FIG. 8, the first peak P1 has a peak top at 1.43 Å, and the second peak P2 has a peak top at 2.40 Å. At a position of 1.43 Å, there is a peak attributed to the interatomic distance of B (boron)-O (oxygen). At a position of 2.40 Å, there is a peak attributed to the interatomic distance of B (boron)-B (boron). In other words, the observation of the above two peaks (the first peak and the second peak) means that a periodic structure corresponding to the above two interatomic distances exists in the specific lithium tetraborate.
[0081] Furthermore, in requirement W, as shown in FIG. 8, when r is in the range of more than 5 Å and not more than 10 Å, the absolute value of G(r) is less than 1.0 (corresponding to the dashed line). As described above, the absolute value of G(r) being less than 1.0 when r is in the range of more than 5 Å and not more than 10 Å means that the specific lithium tetraborate has almost no long-range ordered structure.
[0082] The specific lithium tetraborate satisfying the above requirement W has a short-range ordered structure related to the interatomic distances of BO and BB as described above, but has almost no long-range ordered structure. Therefore, the specific lithium tetraborate itself exhibits elastic properties that are easily plastically deformed.
[0083] In the reduced pair distribution function G(r), there may be a peak other than the first peak and the second peak in the range of r of 5 Å or less.
[0084] In order to obtain a more excellent effect of the present invention, the specific lithium tetraborate preferably satisfies the following requirement V. In other words, the specific lithium tetraborate is preferably a lithium tetraborate that exhibits the characteristics specified in requirement V. Note that requirement V is evaluated by the same procedure as requirement Y of the fourth embodiment described below, except that specific lithium tetraborate is used as the measurement object, and the evaluation method is shown in requirement Y described below. Requirement V: In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of specific lithium tetraborate, none of the following is present: a first peak having a peak top in the range of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, a second peak having a peak top in the range of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, a third peak having a peak top in the range of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and a fourth peak having a peak top in the range of 34.4 to 34.8° and a full width at half maximum of 0.65° or less; or In the X-ray diffraction pattern, when at least one specific peak selected from the group consisting of a first peak, a second peak, a third peak, and a fourth peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: Calculate average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of a specific peak, calculate average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of a specific peak, calculate the arithmetic average of average intensity 1 and average intensity 2, and the ratio of the peak intensity at the peak top of the specific peak to the arithmetic average is the intensity ratio.
[0085] In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of the specific lithium tetraborate, if none of the first peak, second peak, third peak, and fourth peak is present, or if a specific peak selected from the group consisting of the first peak, second peak, third peak, and fourth peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. Among them, if none of the first peak, second peak, third peak, and fourth peak is present, or if a specific peak selected from the group consisting of the first peak, second peak, third peak, and fourth peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less.
[0086] In the above X-ray diffraction pattern of requirement V, if the peak top is located in the range of 21.6 to 22.0° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the first peak and the above requirement V is judged. In addition, in the above X-ray diffraction pattern of requirement V, if the peak top is located in the range of 25.4 to 25.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the second peak and the above requirement V is judged. In addition, in the above X-ray diffraction pattern of requirement V, if the peak top is located in the range of 33.4 to 33.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the third peak and the above requirement V is judged. In addition, in the above X-ray diffraction pattern of requirement V, if the peak top is located in the range of 34.4 to 34.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the fourth peak and the above requirement V is judged.
[0087] In addition, the specific lithium tetraborate preferably satisfies the following requirement T2, in terms of achieving better effects of the present invention. The following requirement T2 is a requirement that is evaluated by the same procedure as requirement T of the first embodiment described above, except that specific lithium tetraborate is used as the measurement object, and the evaluation method is as described above. Requirement T2: In the Raman spectrum of a specific lithium tetraborate, the peak at 710 to 730 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The first peak above, 770-790 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The second peak above and 1020-1040 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 None of the above third peaks are present, or In the above Raman spectrum, when at least one specific peak selected from the group consisting of a first peak, a second peak, and a third peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: 400 to 600 cm of the above Raman spectrum -1 The point showing the minimum value M1 of the Raman intensity in the wavenumber region of 1300 to 1500 cm in the above Raman spectrum -1 A straight line is drawn by connecting the points showing the minimum value M2 of the Raman intensity in the wave number region of 710 to 730 cm in the region from the wave number showing the minimum value M1 to the wave number showing the minimum value M2. -1 , 770~790cm -1 , and 1020~1040cm -1An average difference value between the Raman intensity of the straight line and the Raman intensity of the Raman spectrum at each wavenumber in the region other than the region is calculated, and an absolute value of the difference between the Raman intensity of the peak at the wavenumber showing the peak top of the specific peak and the Raman intensity of the straight line is calculated, and the ratio of the absolute value of the difference to the average difference value is defined as the intensity ratio.
[0088] In the Raman spectrum of the specific lithium tetraborate, when the first peak, the second peak, and the third peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. Among them, when the first peak, the second peak, and the third peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less, and it is particularly preferable that the first peak, the second peak, and the third peak are not present.
[0089] In the third embodiment of the lithium-based solid electrolyte of the present invention, the content of the specific lithium tetraborate is not particularly limited.
[0090] (water) A third embodiment of the lithium-based solid electrolyte of the present invention contains water. In the third embodiment of the lithium-based solid electrolyte of the present invention, the content of water is not particularly limited. In particular, in terms of more excellent effects of the present invention, the molar ratio of water to the specific lithium tetraborate in the third embodiment of the lithium-based solid electrolyte of the present invention (molar amount of water / molar amount of specific lithium tetraborate) is preferably 3 to 15, more preferably 4 to 13, further preferably 5 to 13, and particularly preferably 10 to 13.
[0091] (Lithium salts) A third embodiment of the lithium-based solid electrolyte of the present invention comprises a lithium salt. The type of lithium salt is not particularly limited, and examples thereof include the lithium salts exemplified in Step 1A described below, which will be described in detail later. In the third embodiment of the lithium-based solid electrolyte of the present invention, the content of the lithium salt is not particularly limited. In the third embodiment of the lithium-based solid electrolyte of the present invention, the mass ratio of the content of the lithium salt to the content of the specific lithium tetraborate described above (lithium salt content mass / specific lithium tetraborate content mass) is not particularly limited. In particular, in terms of the superior effect of the present invention, the molar ratio of the lithium salt to the specific lithium tetraborate (lithium salt molar amount / specific lithium tetraborate molar amount) in the third embodiment of the lithium-based solid electrolyte of the present invention is preferably 0.001 to 1.5, more preferably 0.001 to 1.2, even more preferably 0.01 to 1.2, particularly preferably 0.1 to 1.2, and most preferably 0.5 to 1.2.
[0092] The molar ratio of each component in the lithium-based solid electrolyte according to the third embodiment of the present invention can be determined by a known method, for example, the elemental analysis described in the first embodiment above.
[0093] In addition, the solid electrolyte of the third embodiment of the lithium-based solid electrolyte of the present invention is more excellent in the effect of the present invention. 7 The solid of the third embodiment of the lithium-based solid electrolyte of the present invention is a solid of the third embodiment of the lithium-based solid electrolyte of the present invention, with respect to the full width at half maximum of the peak appearing in the chemical shift range of -100 to +100 ppm in the spectrum obtained when Li-NMR measurement is performed at 20 ° C. 7 The ratio of the full width at half maximum of the peak appearing in the chemical shift range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement at 120°C is preferably 50% or less, more preferably 40% or less, and even more preferably 35% or less. There is no particular lower limit, but it is often 10% or more. The full width at half maximum (FWHM) of a peak refers to the width (ppm) at half the height (H) of the peak (H / 2). The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0094] In addition, the solid electrolyte of the third embodiment of the lithium-based solid electrolyte of the present invention is more excellent in the effect of the present invention. 7 When a spectrum obtained by Li-NMR measurement at 20°C is subjected to waveform separation of a first peak appearing in the range of -100 to +100 ppm, it is preferable that a second peak with a chemical shift in the range of -3 to 3 ppm and a full width at half maximum of 5 ppm or less is present, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more. The ratio of the area intensity is more preferably 2% or more, and further preferably 15% or more. There is no particular upper limit to the ratio of the area intensity, but it is often 50% or less. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0095] In addition, in terms of the superior effect of the present invention, in the infrared absorption spectrum of the third embodiment of the lithium-based solid electrolyte of the present invention, -1 The maximum absorption intensity in the wavenumber region of 3000 to 3500 cm -1 The ratio of the maximum absorption intensity in the wave number region of is preferably 1 / 5 or more. In particular, in terms of the superior effect of the present invention, the ratio is preferably 3 / 10 or more, and more preferably 2 / 5 or more. There is no particular upper limit, but it is preferably 1 or less. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0096] In addition, the effect of the present invention is more excellent in that the range of 600 to 850 cm in the Raman spectrum of the third embodiment of the lithium-based solid electrolyte of the present invention is -1 The coefficient of determination obtained by performing linear regression analysis by the least squares method in the wave number region is preferably 0.9400 or more. In addition, the coefficient of determination is more preferably 0.9600 or more in terms of the effect of the present invention being more excellent. The upper limit is not particularly limited, but may be 1.0000. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment. In addition, in terms of obtaining better effects of the present invention, it is preferable that the third embodiment of the lithium-based solid electrolyte of the present invention satisfies requirement T. The following requirement T is the same as the requirement T defined in the above-mentioned first embodiment, and the measurement method thereof is also as explained in the first embodiment. Requirement T: In the Raman spectrum of lithium-based solid electrolytes, the peak intensity is 710 to 730 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The first peak above, 770-790 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The second peak above and 1020-1040 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 None of the above third peaks are present, or In the above Raman spectrum, when at least one specific peak selected from the group consisting of a first peak, a second peak, and a third peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: 400 to 600 cm of the above Raman spectrum -1 The point showing the minimum value M1 of the Raman intensity in the wavenumber region of 1300 to 1500 cm in the above Raman spectrum -1 A straight line is drawn by connecting the points showing the minimum value M2 of the Raman intensity in the wave number region of 710 to 730 cm in the region from the wave number showing the minimum value M1 to the wave number showing the minimum value M2. -1 , 770~790cm -1 , and 1020~1040cm -1 An average difference value between the Raman intensity of the straight line and the Raman intensity of the Raman spectrum at each wavenumber in the region other than the region is calculated, and an absolute value of the difference between the Raman intensity of the peak at the wavenumber showing the peak top of the specific peak and the Raman intensity of the straight line is calculated, and the ratio of the absolute value of the difference to the average difference value is defined as the intensity ratio.
[0097] In the Raman spectrum of the lithium-based solid electrolyte, when the first peak, the second peak, and the third peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. In particular, when the first peak, the second peak, and the third peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less, and it is particularly preferable that the first peak, the second peak, and the third peak are not present.
[0098] In order to obtain a more excellent effect of the present invention, the mass loss rate of the third embodiment of the lithium-based solid electrolyte of the present invention when heated to 800° C. is preferably 20 to 40% by mass. In particular, in order to obtain a more excellent effect of the present invention, the mass loss rate is more preferably 25 to 35% by mass. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0099] The bulk modulus of the third embodiment of the lithium-based solid electrolyte of the present invention is not particularly limited, but is preferably 45 GPa or less, more preferably 40 GPa or less, in terms of the superior effect of the present invention. The lower limit is not particularly limited, but is preferably 5 GPa or more. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment. The preferred range of the bulk modulus of the specific lithium tetraborate is also the same as the preferred range of the bulk modulus of the lithium-based solid electrolyte according to the third embodiment of the present invention.
[0100] The median diameter (D50) of the third embodiment of the lithium-based solid electrolyte of the present invention is not particularly limited, but is preferably 0.01 to 20 μm, more preferably 0.1 to 2.0 μm, in terms of better effects of the present invention. The median diameter (D50) was measured by obtaining particle images by flow particle image analysis, calculating the particle diameter distribution of the third embodiment of the lithium-based solid electrolyte of the present invention, and analyzing the obtained distribution. The particle diameter corresponds to the circle equivalent diameter.
[0101] In order to obtain a more excellent effect of the present invention, the third embodiment of the lithium-based solid electrolyte of the present invention preferably satisfies the following requirement X. The following requirement X is the same as the requirement X defined in the fourth embodiment described later, and will be described in detail later. Requirement X: In the reduced pair distribution function G(r) obtained from X-ray total scattering measurement of the lithium-based solid electrolyte, there is a first peak whose peak top is located in an r range of 1.43±0.2 Å and a second peak whose peak top is located in an r range of 2.40±0.2 Å, and the G(r) at the peak top of the first peak is greater than 1.0 (preferably 1.2 or greater), and the G(r) at the peak top of the second peak is 0.8 or greater (preferably greater than 1.0).
[0102] In order to obtain a more excellent effect of the present invention, the third embodiment of the lithium-based solid electrolyte of the present invention preferably satisfies the following requirement Y. The following requirement Y is the same as the requirement Y defined in the fourth embodiment described later, and will be described in detail later. Requirement Y: In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of a lithium-based solid electrolyte, none of the following peaks are present: a first peak having a peak top in the range of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, a second peak having a peak top in the range of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, a third peak having a peak top in the range of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and a fourth peak having a peak top in the range of 34.4 to 34.8° and a full width at half maximum of 0.65° or less; or In the X-ray diffraction pattern, when at least one specific peak selected from the group consisting of a first peak, a second peak, a third peak, and a fourth peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: Calculate average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of a specific peak, calculate average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of a specific peak, calculate the arithmetic average of average intensity 1 and average intensity 2, and the ratio of the peak intensity at the peak top of the specific peak to the arithmetic average is the intensity ratio.
[0103] In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of the third embodiment of the lithium-based solid electrolyte, if none of the first peak, the second peak, the third peak, and the fourth peak is present, or if a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. Among them, if none of the first peak, the second peak, the third peak, and the fourth peak is present, or if a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less.
[0104] (Another version) In the above, the third embodiment has been described as using the specific lithium tetraborate, but the third embodiment may use amorphous lithium tetraborate instead of the specific lithium tetraborate. That is, the third embodiment of the lithium-based solid electrolyte of the present invention may include amorphous lithium tetraborate, water, and a lithium salt. Amorphous lithium tetraborate means lithium tetraborate that satisfies at least one of requirements S1 to S3. Requirement S1 is a requirement that is evaluated by the same procedure as requirement W described above, except that amorphous lithium tetraborate is used as the measurement object, and the evaluation method is as described above. Moreover, requirement S2 is a requirement that is evaluated by the same procedure as requirement T described above, except that amorphous lithium tetraborate is used as the measurement object, and the evaluation method is as described above. Furthermore, requirement S3 is a requirement that is evaluated by a procedure similar to that of requirement Y of the fourth embodiment described below, except that amorphous lithium tetraborate is used as the measurement object, and the evaluation method is shown in requirement Y described below.
[0105] Requirement S1: In the reduced pair distribution function G(r) obtained from X-ray total scattering measurement of amorphous lithium tetraborate, there is a first peak whose peak top is located in the r range of 1.43 ± 0.2 Å and a second peak whose peak top is located in the r range of 2.40 ± 0.2 Å, and the G(r) at the peak top of the first peak and the G(r) at the peak top of the second peak are greater than 1.0, and the absolute value of G(r) is less than 1.0 when r is in the range of greater than 5 Å and not more than 10 Å. Requirement S2: In the Raman spectrum of amorphous lithium tetraborate, the peak at 710 to 730 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The first peak above, 770-790 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The second peak above and 1020-1040 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 None of the above third peaks are present, or In the above Raman spectrum, when at least one specific peak selected from the group consisting of a first peak, a second peak, and a third peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: 400 to 600 cm of the above Raman spectrum -1 The point showing the minimum value M1 of the Raman intensity in the wavenumber region of 1300 to 1500 cm in the above Raman spectrum -1 A straight line is drawn by connecting the points showing the minimum value M2 of the Raman intensity in the wave number region of 710 to 730 cm in the region from the wave number showing the minimum value M1 to the wave number showing the minimum value M2. -1 , 770~790cm -1 , and 1020~1040cm -1An average difference value between the Raman intensity of the straight line and the Raman intensity of the Raman spectrum at each wavenumber in the region other than the region is calculated, and an absolute value of the difference between the Raman intensity of the peak at the wavenumber showing the peak top of the specific peak and the Raman intensity of the straight line is calculated, and the ratio of the absolute value of the difference to the average difference value is defined as the intensity ratio. Requirement S3: In the X-ray diffraction pattern obtained by X-ray diffraction measurement of amorphous lithium tetraborate using CuKα radiation, none of the following peaks are present: a first peak having a peak top in the range of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, a second peak having a peak top in the range of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, a third peak having a peak top in the range of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and a fourth peak having a peak top in the range of 34.4 to 34.8° and a full width at half maximum of 0.65° or less; or In the X-ray diffraction pattern, when at least one specific peak selected from the group consisting of a first peak, a second peak, a third peak, and a fourth peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: Calculate average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of a specific peak, calculate average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of a specific peak, calculate the arithmetic average of average intensity 1 and average intensity 2, and the ratio of the peak intensity at the peak top of the specific peak to the arithmetic average is the intensity ratio.
[0106] In the Raman spectrum of the amorphous lithium tetraborate satisfying the requirement S2, if none of the first peak, the second peak, and the third peak is present, or if a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. In particular, if none of the first peak, the second peak, and the third peak is present, or if a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less, and it is particularly preferable that none of the first peak, the second peak, and the third peak is present.
[0107] In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of the specific lithium tetraborate of requirement S3, if none of the first peak, second peak, third peak, and fourth peak is present, or if a specific peak selected from the group consisting of the first peak, second peak, third peak, and fourth peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. Among them, if none of the first peak, second peak, third peak, and fourth peak is present, or if a specific peak selected from the group consisting of the first peak, second peak, third peak, and fourth peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less.
[0108] In the above X-ray diffraction pattern of requirement S3, if the peak top is located in the range of 21.6 to 22.0° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the first peak and the above requirement S3 is judged. In addition, in the above X-ray diffraction pattern of requirement S3, if the peak top is located in the range of 25.4 to 25.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the second peak and the above requirement S3 is judged. In addition, in the above X-ray diffraction pattern of requirement S3, if the peak top is located in the range of 33.4 to 33.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the third peak and the above requirement S3 is judged. In addition, in the above X-ray diffraction pattern of requirement S3, if the peak top is located in the range of 34.4 to 34.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the fourth peak and the above requirement S3 is judged.
[0109] In addition, in a lithium-based solid electrolyte containing amorphous lithium tetraborate, water, and a lithium salt, the relationship between the content of amorphous lithium tetraborate and other components (for example, water and lithium salt) satisfies the same content relationship as when the specific lithium tetraborate described above is used. That is, the molar ratio of the lithium salt to the amorphous lithium tetraborate is preferably 0.001 to 1.5, and the molar ratio of the water to the amorphous lithium tetraborate is preferably 3 to 15, and the preferred ranges of each molar ratio are the same as the preferred ranges of the molar ratio of the lithium salt to the specific lithium tetraborate described above and the molar ratio of the water to the amorphous lithium tetraborate. In addition, the lithium-based solid electrolyte containing amorphous lithium tetraborate, water, and a lithium salt preferably exhibits the various characteristics described in the third embodiment using the specific lithium tetraborate described above. Specific examples of the various characteristics include the following items described above, and the preferred ranges thereof are as described above. Lithium-based solid electrolyte 7 The solid state of lithium-based solid electrolytes is shown in Fig. 1. The solid state of lithium-based solid electrolytes is shown in Fig. 1. The solid state of lithium-based solid electrolytes is shown in Fig. 1. 7 The ratio of the full width at half maximum of the peaks that appear in the chemical shift range of -100 to +100 ppm in the spectrum obtained when Li-NMR measurement is performed at 120°C Lithium-based solid electrolyte 7When the first peak appears in the range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement at 20°C, it is subjected to waveform separation, and there is a second peak with a chemical shift in the range of -3 to 3 ppm and a full width at half maximum of 5 ppm or less, and the ratio of the area intensity of the second peak to the area intensity of the first peak is In the infrared absorption spectrum of lithium-based solid electrolytes, the wavelength range is 800 to 1600 cm -1 The maximum absorption intensity in the wavenumber region of 3000 to 3500 cm -1 Ratio of maximum absorption intensities in the wavenumber region of Raman spectrum of lithium-based solid electrolytes from 600 to 850 cm -1 The coefficient of determination obtained by linear regression analysis using the least squares method in the wavenumber domain of Mass loss rate of lithium-based solid electrolyte when heated to 800℃ Bulk modulus of lithium-based solid electrolyte · Median diameter of lithium-based solid electrolyte (D50)
[0110] In addition, the lithium-based solid electrolyte containing amorphous lithium tetraborate, water, and a lithium salt preferably satisfies at least one of requirements X, Y, and T, similarly to the lithium-based solid electrolyte containing the specific lithium tetraborate described above.
[0111] In addition, in the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation under the requirement Y satisfied by the lithium-based solid electrolyte containing the amorphous lithium tetraborate, if none of the first peak, the second peak, the third peak, and the fourth peak is present, or if a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. In particular, if none of the first peak, the second peak, the third peak, and the fourth peak is present, or if a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less.
[0112] In addition, in the Raman spectrum at the requirement T satisfied by the lithium-based solid electrolyte containing the amorphous lithium tetraborate, if none of the first peak, the second peak, and the third peak are present, or if a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. Among them, if none of the first peak, the second peak, and the third peak are present, or if a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less, and it is particularly preferable that none of the first peak, the second peak, and the third peak are present.
[0113] <<Fourth embodiment>> A fourth embodiment of the lithium-based solid electrolyte of the present invention contains Li, B, and O, and satisfies all of the requirements X to Z. Requirements X to Z are explained in detail below.
[0114] The fourth embodiment of the lithium-based solid electrolyte of the present invention satisfies the following requirement X. Requirement X: In the reduced pair distribution function G(r) obtained from X-ray total scattering measurement of the lithium-based solid electrolyte, there is a first peak whose peak top is located in an r range of 1.43±0.2 Å and a second peak whose peak top is located in an r range of 2.40±0.2 Å, and the G(r) at the peak top of the first peak is greater than 1.0 (preferably 1.2 or greater), and the G(r) at the peak top of the second peak is 0.8 or greater (preferably greater than 1.0). Requirement X corresponds to a part of the requirement W described above, and its technical meaning, as described above, is that a periodic structure corresponding to the interatomic distance of B (boron)-O (oxygen) and the interatomic distance of B (boron)-B (boron) is present in the lithium-based solid electrolyte. Requirement X differs from requirement W in that G(r) at the peak top of the second peak is 0.8 or more. As described above, requirement X preferably has G(r) at the peak top of the first peak of 1.2 or more, and preferably has G(r) at the peak top of the second peak of more than 1.0. The measurement method for requirement X is the same as requirement W described above. FIG. 16 shows an example of the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement of the fourth embodiment of the lithium-based solid electrolyte of the present invention.
[0115] The fourth embodiment of the lithium-based solid electrolyte of the present invention satisfies the following requirement Y. Requirement Y: In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of a lithium-based solid electrolyte, none of the following peaks are present: a first peak having a peak top in the range of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, a second peak having a peak top in the range of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, a third peak having a peak top in the range of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and a fourth peak having a peak top in the range of 34.4 to 34.8° and a full width at half maximum of 0.65° or less; or In the X-ray diffraction pattern, when at least one specific peak selected from the group consisting of a first peak, a second peak, a third peak, and a fourth peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: Calculate average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of a specific peak, calculate average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of a specific peak, calculate the arithmetic average of average intensity 1 and average intensity 2, and the ratio of the peak intensity at the peak top of the specific peak to the arithmetic average is the intensity ratio. Requirement Y will be explained below.
[0116] First, requirement Y is met when an X-ray diffraction pattern obtained from an X-ray diffraction measurement of a lithium-based solid electrolyte using CuKα radiation does not include a first peak having a peak top in the range of 21.6 to 22.0° and a full width at half maximum of 0.65° or less, a second peak having a peak top in the range of 25.4 to 25.8° and a full width at half maximum of 0.65° or less, a third peak having a peak top in the range of 33.4 to 33.8° and a full width at half maximum of 0.65° or less, and a fourth peak having a peak top in the range of 34.4 to 34.8° and a full width at half maximum of 0.65° or less. The full width at half maximum (FWHM) of a peak refers to the width (in degrees) of the peak at half its intensity.
[0117] In addition, when at least one specific peak selected from the group consisting of a first peak, a second peak, a third peak, and a fourth peak is present in an X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation for a lithium-based solid electrolyte, requirement Y is also satisfied when the intensity ratio of at least one of the specific peaks calculated by the intensity measurement method described below is 5.0 or less. The strength measurement method will be explained below with reference to FIG. Fig. 11 is a diagram showing an example of a specific peak appearing in a diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of a fourth embodiment of a lithium-based solid electrolyte. In the diffraction pattern shown in Fig. 11, a specific peak is shown whose peak top intensity is intensity 1. In the intensity measurement method, as shown in Fig. 11, an average intensity 1 is calculated in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of the specific peak, and an average intensity 2 is calculated in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of the specific peak. Next, the arithmetic average value of the average intensity 1 and the average intensity 2 is calculated, and the ratio of the intensity 1 to the arithmetic average value is obtained as the intensity ratio. When the above requirement Y is satisfied, this means that no or almost no crystal structure exists in the lithium-based solid electrolyte, and the electrolyte is in an amorphous state. That is, the first to fourth peaks described in requirement Y are mainly peaks derived from the crystal structure in the lithium-based solid electrolyte (particularly, the crystal structure of lithium tetraborate), and when these peaks are not present, the lithium-based solid electrolyte does not have a specific crystal structure and is in an amorphous state, so it is presumed that, as described above, a hydrated layer with excellent ion conductivity is easily formed. Even when at least one of the first to fourth peaks is present, the intensity ratio of any one of the specific peaks present is equal to or less than a specific value, which indicates that the lithium-based solid electrolyte has almost no crystal structure, and it is presumed that, as described above, a hydrated layer with excellent ion conductivity is easily formed. In addition, in the lithium-based solid electrolyte, a peak due to other factors may occur in addition to the peak derived from a specific crystal structure such as the crystal structure of lithium tetraborate given as an example. Examples of other factors include peaks derived from specific components (e.g., lithium salts), and such peaks may overlap with the first to fourth peaks described above. When an amorphous state is achieved that is presumed to be capable of forming a hydration layer with excellent ion conductivity, all of the first to fourth peaks are often reduced. Even if, as described above, a peak due to another factor happens to overlap with any of the first to fourth peaks to produce a large peak, the presence of a specific peak whose intensity ratio is equal to or less than a predetermined value indicates that the lithium-based solid electrolyte is in an amorphous state that is presumed to be capable of forming a hydration layer with excellent ion conductivity.
[0118] The X-ray diffraction measurement is carried out using CuKα radiation under measurement conditions of 0.01° / step and 3° / min.
[0119] In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of the fourth embodiment of the lithium-based solid electrolyte, when the first peak, the second peak, the third peak, and the fourth peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. Among them, when the first peak, the second peak, the third peak, and the fourth peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less.
[0120] In the above X-ray diffraction pattern of requirement Y, if the peak top is located in the range of 21.6 to 22.0° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the first peak and the above requirement Y is judged. In addition, in the above X-ray diffraction pattern of requirement Y, if the peak top is located in the range of 25.4 to 25.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the second peak and the above requirement Y is judged. In addition, in the above X-ray diffraction pattern of requirement Y, if the peak top is located in the range of 33.4 to 33.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the third peak and the above requirement Y is judged. In addition, in the above X-ray diffraction pattern of requirement Y, if the peak top is located in the range of 34.4 to 34.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the fourth peak and the above requirement Y is judged.
[0121] The fourth embodiment of the lithium-based solid electrolyte of the present invention satisfies the following requirement Z. Requirement Z: In the infrared absorption spectrum of the fourth embodiment of the lithium-based solid electrolyte, -1The maximum absorption intensity in the wavenumber region of 3000 to 3500 cm -1 The ratio of the maximum absorption intensity in the wave number region of is 1 / 5 or more. The above requirement Z is the same as the characteristic explained in the first embodiment, and the preferable range and the measuring method thereof are also as described above.
[0122] In the fourth embodiment of the lithium-based solid electrolyte of the present invention, when the molar amount of B in the lithium-based solid electrolyte is 4.00 and the molar amount of Li is expressed, the molar amount of Li is preferably 1.58 to 3.49. In other words, when the molar amount of B contained is 4.00, the relative value of the molar amount of Li contained is preferably 1.58 to 3.49. In particular, in terms of superior effects of the present invention, when the molar amount of B in the lithium-based solid electrolyte is taken as 4.00 and the molar amount of Li is expressed, the molar amount of Li is more preferably 1.58 to 3.00, further preferably 1.90 to 3.00, and particularly preferably 2.00 to 3.00.
[0123] In the fourth embodiment of the lithium-based solid electrolyte of the present invention, when the molar amount of B in the lithium-based solid electrolyte is 4.00 and the molar amount of O is expressed, the molar amount of O is preferably 6.23 to 25.00. In other words, when the molar amount of B contained is 4.00, the relative value of the molar amount of O contained is preferably 6.23 to 25.00. Among these, in terms of superior effects of the present invention, when the molar amount of B in the lithium-based solid electrolyte is taken as 4.00 and the molar amount of O is expressed, the molar amount of O is more preferably 10.00 to 23.00.
[0124] The fourth embodiment of the lithium-based solid electrolyte of the present invention further contains preferably one or more specific elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N, and more preferably contains two or more specific elements. In the fourth embodiment of the lithium-based solid electrolyte of the present invention, when the molar amount of B in the lithium-based solid electrolyte is 4.00 and the molar amount of each specific element is expressed, the molar amount of each specific element is preferably 0.001 to 10.00. In other words, when the molar amount of B contained is 4.00, the relative value of the molar amount of each specific element contained is preferably 0.001 to 10.00. In particular, in terms of superior effects of the present invention, when the molar amount of B in the lithium-based solid electrolyte is taken as 4.00 and the molar amount of each specific element is expressed, the molar amount of each specific element is more preferably 0.001 to 6.0, and even more preferably 0.01 to 5.0. As described above, in the fourth embodiment of the lithium-based solid electrolyte of the present invention, it is preferable that two or more specific elements are included. Therefore, for example, when the fourth embodiment of the lithium-based solid electrolyte of the present invention includes two specific elements, a specific element A and a specific element B which is a different type of element from the specific element A, when the molar amount of B in the lithium-based solid electrolyte is 4.00, the molar amount of the specific element A and the molar amount of the specific element B are each preferably 0.001 to 10.00. Also, for example, when the fourth embodiment of the lithium-based solid electrolyte of the present invention includes three specific elements, a specific element A, a specific element B which is a different type of element from the specific element A, and a specific element C which is a different type of element from the specific elements A and B, when the molar amount of B in the lithium-based solid electrolyte is 4.00, the molar amount of the specific element A, the molar amount of the specific element B, and the molar amount of the specific element C are each preferably 0.001 to 10.00.
[0125] The contents of Li, B, and the specific element in the fourth embodiment of the lithium-based solid electrolyte of the present invention are determined by known elemental analysis. As an elemental analysis method, for example, Li and B are analyzed by ICP-OES (Inductively Coupled Plasma Optical Emission Spectrometry), N, which is one of the specific elements, is analyzed by an inert gas fusion method, and F and S, which are one of the specific elements, are analyzed by combustion ion chromatography. O can be calculated by adding up the analyzed masses of elements other than O and calculating the difference from the total amount of powder. Note that the calculation method of the content of each element is not limited to the above, and the content of one element may be estimated from the analysis result of the content of another element, taking into account the structure of the compound used. From the contents of the respective elements calculated by elemental analysis, the molar amounts of Li, O, and the specific element are calculated when the molar amount of B is set to 4.00.
[0126] One of the preferable modes of the composition of the fourth embodiment of the lithium-based solid electrolyte of the present invention includes a lithium-based solid electrolyte containing Li, B, O, F, S, and N, in which, when the molar amount of B is 4.00, the molar amount of Li is 1.58 to 3.49 (preferably, 1.58 to 3.00), the molar amount of O is 6.23 to 25.00, the molar amount of F is 0.001 to 10.00, the molar amount of S is 0.001 to 2.00, and the molar amount of N is 0.001 to 1.00. The preferred range of the molar ratio is as described above.
[0127] The fourth embodiment of the lithium-based solid electrolyte of the present invention may contain elements other than Li, B, O, and the specific element.
[0128] The manufacturing method of the fourth embodiment of the lithium-based solid electrolyte of the present invention will be described in detail later, but the lithium-based solid electrolyte of the present invention is preferably manufactured by a manufacturing method involving mechanical milling. For example, it is presumed that by performing mechanical milling on the raw material of the fourth embodiment of the lithium-based solid electrolyte of the present invention (e.g., lithium-based oxide containing Li and B), the crystalline component in the raw material can be made amorphous, and as a result, it becomes easier to form a hydration layer with excellent ion conductivity.
[0129] In addition, the solid electrolyte of the fourth embodiment of the lithium-based solid electrolyte of the present invention is more excellent in the effect of the present invention. 7 The solid of the fourth embodiment of the lithium-based solid electrolyte of the present invention is a solid of the fourth embodiment of the lithium-based solid electrolyte of the present invention, with respect to the full width at half maximum of the peak appearing in the chemical shift range of -100 to +100 ppm in the spectrum obtained when Li-NMR measurement is performed at 20 ° C. 7 The ratio of the full width at half maximum of the peak appearing in the chemical shift range of -100 to +100 ppm in the spectrum obtained by Li-NMR measurement at 120°C is preferably 50% or less, more preferably 40% or less, and even more preferably 35% or less. There is no particular lower limit, but it is often 10% or more. The full width at half maximum (FWHM) of a peak refers to the width (ppm) at half the height (H) of the peak (H / 2). The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0130] In addition, the solid electrolyte of the fourth embodiment of the lithium-based solid electrolyte of the present invention is more excellent in the effect of the present invention. 7 When a spectrum obtained by Li-NMR measurement at 20°C is subjected to waveform separation of a first peak appearing in the range of -100 to +100 ppm, it is preferable that a second peak with a chemical shift in the range of -3 to 3 ppm and a full width at half maximum of 5 ppm or less is present, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more. The ratio of the area intensity is more preferably 2% or more, and further preferably 15% or more. There is no particular upper limit to the ratio of the area intensity, but it is often 50% or less. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0131] In addition, the effect of the present invention is more excellent in the range of 600 to 850 cm in the Raman spectrum of the fourth embodiment of the lithium-based solid electrolyte of the present invention. -1 The coefficient of determination obtained by performing linear regression analysis by the least squares method in the wave number region is preferably 0.9400 or more. In addition, the coefficient of determination is more preferably 0.9600 or more in terms of the effect of the present invention being more excellent. The upper limit is not particularly limited, but may be 1.0000. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment. In addition, in terms of obtaining better effects of the present invention, it is preferable that the fourth embodiment of the lithium-based solid electrolyte of the present invention satisfies requirement T. The following requirement T is the same as the requirement T defined in the above-mentioned first embodiment, and the measurement method thereof is also as explained in the first embodiment. Requirement T: In the Raman spectrum of lithium-based solid electrolytes, the peak intensity is 710 to 730 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The first peak above, 770-790 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The second peak above and 1020-1040 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 None of the above third peaks are present, or In the above Raman spectrum, when at least one specific peak selected from the group consisting of a first peak, a second peak, and a third peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: 400 to 600 cm of the above Raman spectrum -1 The point showing the minimum value M1 of the Raman intensity in the wavenumber region of 1300 to 1500 cm in the above Raman spectrum -1A straight line is drawn by connecting the points showing the minimum value M2 of the Raman intensity in the wave number region of 710 to 730 cm in the region from the wave number showing the minimum value M1 to the wave number showing the minimum value M2. -1 , 770~790cm -1 , and 1020~1040cm -1 An average difference value between the Raman intensity of the straight line and the Raman intensity of the Raman spectrum at each wavenumber in the region other than the region is calculated, and an absolute value of the difference between the Raman intensity of the peak at the wavenumber showing the peak top of the specific peak and the Raman intensity of the straight line is calculated, and the ratio of the absolute value of the difference to the average difference value is defined as the intensity ratio.
[0132] In the Raman spectrum of the lithium-based solid electrolyte, when the first peak, the second peak, and the third peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. In particular, when the first peak, the second peak, and the third peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is even more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less, and it is particularly preferable that the first peak, the second peak, and the third peak are not present.
[0133] In order to obtain a more excellent effect of the present invention, the mass loss rate of the fourth embodiment of the lithium-based solid electrolyte of the present invention when heated to 800° C. is preferably 20 to 40% by mass. In particular, in order to obtain a more excellent effect of the present invention, the mass loss rate is more preferably 25 to 35% by mass. The above characteristics are as explained in the first embodiment, and the method for measuring them is also as explained in the first embodiment.
[0134] The bulk modulus of the fourth embodiment of the lithium-based solid electrolyte of the present invention is not particularly limited, but is preferably 45 GPa or less, more preferably 40 GPa or less, in terms of the superior effect of the present invention. The lower limit is not particularly limited, but is preferably 5 GPa or more. The above characteristics are as described in the first embodiment, and the measurement method thereof is also as described in the first embodiment.
[0135] The median diameter (D50) of the fourth embodiment of the lithium-based solid electrolyte of the present invention is not particularly limited, but in terms of more excellent effects of the present invention, 0.01 to 20 μm is preferable, and 0.1 to 2.0 μm is more preferable. The measurement method of the above median diameter (D50) is to obtain particle images by a flow type particle image analysis method, calculate the particle size distribution of the fourth embodiment of the lithium-based solid electrolyte of the present invention, and analyze from the obtained distribution. The above particle size corresponds to the equivalent circle diameter.
[0136] <<Fifth Embodiment>> The fifth embodiment of the lithium-based solid electrolyte of the present invention is an amorphous LiB3O5, Li3B 11 O 18 or Li3B7O 12 and contains water and a lithium salt. Hereinafter, each component will be described in detail.
[0137] (Amorphous LiB3O5, Li3B 11 O 18 or Li3B7O 12 (hereinafter also referred to as "specific boric acid compound").) The fifth embodiment of the lithium-based solid electrolyte of the present invention contains amorphous LiB3O5, Li3B 11 O 18 or Li3B7O 12 . The compound represented by LiB3O5 is mainly a compound composed of Li, B, and O, but in the present invention, it may deviate from the above standard value. More specifically, Li 1+x B 3+y O 5+z (-0.3 < x < 0.3, -0.3 < y < 0.3, -0.3 < z < 0.3) is preferably represented by the compound. Li3B 11 O 18The compound represented by is mainly a compound composed of Li, B, and O. However, in the present invention, it may deviate from the above standard values. More specifically, Li 3+x B 11+y O 18+z (-0.3 < x < 0.3, -0.3 < y < 0.3, -0.3 < z < 0.3) is preferred. Li3B7O 12 The compound represented by is mainly a compound composed of Li, B, and O. However, in the present invention, it may deviate from the above standard values. More specifically, Li 3+x B 7+y O 12+z (-0.3 < x < 0.3, -0.3 < y < 0.3, -0.3 < z < 0.3) is preferred.
[0138] Amorphous LiB3O5 means LiB3O5 that satisfies the following requirement Y2. Requirement Y2: In the X-ray diffraction pattern obtained from the X-ray diffraction measurement using the CuKα ray of LiB3O5, the peak top is located in the range of 15.4 to 15.8°, the first peak with a full width at half maximum of 0.65° or less, the peak top is located in the range of 23.4 to 23.8°, the second peak with a full width at half maximum of 0.65° or less, the peak top is located in the range of 26.8 to 27.2°, the third peak with a full width at half maximum of 0.65° or less, and the peak top is located in the range of 29.4 to 29.8°, and none of the fourth peaks with a full width at half maximum of 0.65° or less exist, or in the X-ray diffraction pattern, when at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak exists, the intensity ratio calculated by at least one of the following intensity measurement methods of the specific peak is 5.0 or less. Intensity measurement method: Calculate the average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of the specific peak, calculate the average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of the specific peak, calculate the additive average value of the above average intensity 1 and the above average intensity 2, and use the ratio of the peak intensity at the peak top of the specific peak to the above additive average value as the intensity ratio.
[0139] In particular, in the requirement Y2, in the X-ray diffraction pattern obtained by X-ray diffraction measurement of LiB3O5 using CuKα radiation, it is preferable that the first peak, the second peak, the third peak, and the fourth peak are not present, or if a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, the intensity ratio of at least one of the specific peaks is 3.0 or less. In particular, it is more preferable that the first peak, the second peak, the third peak, and the fourth peak are not present, or if a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, the intensity ratio of at least one of the specific peaks is 2.0 or less.
[0140] Amorphous Li3B 11 O 18 Li3B that meets the following requirement Y3 11 O 18 means. Requirement Y3:Li3B 11 O 18 In an X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα ray, none of the following is present: a first peak having a peak top in the range of 19.7 to 20.1° and a full width at half maximum of 0.65° or less, a second peak having a peak top in the range of 22.3 to 22.7° and a full width at half maximum of 0.65° or less, and a third peak having a peak top in the range of 27.3 to 27.7° and a full width at half maximum of 0.65° or less; or, when at least one specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present in the X-ray diffraction pattern, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: Calculate average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of a specific peak, calculate average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of a specific peak, calculate the arithmetic average of the average intensities 1 and 2, and define the ratio of the peak intensity at the peak top of the specific peak to the arithmetic average as the intensity ratio.
[0141] Among them, in requirement Y3, Li3B 11 O 18 In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation, when the first, second and third peaks are not present or when a specific peak selected from the group consisting of the first, second and third peaks is present, it is preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. In particular, when the first, second and third peaks are not present or when a specific peak selected from the group consisting of the first, second and third peaks is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less.
[0142] Amorphous Li3B7O 12 Li3B7O that satisfies the following requirement Y4 12 means. Requirement Y4: Li3B7O 12 In an X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα ray, the peak top is located in the range of 16.5 to 16.9°, and no first peak having a full width at half maximum of 0.65° or less is present, or, if a first peak is present in the X-ray diffraction pattern, the intensity ratio of at least one of the first peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: Calculate average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of a specific peak, calculate average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of a specific peak, calculate the arithmetic average of the average intensities 1 and 2, and define the ratio of the peak intensity at the peak top of the specific peak to the arithmetic average as the intensity ratio.
[0143] Among them, requirement Y4 requires Li3B7O 12In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation, it is preferable that the first peak does not exist, or if the first peak exists, the intensity ratio of the first peak is 3.0 or less. In particular, it is more preferable that the first peak does not exist, or if the first peak exists, the intensity ratio of the first peak is 2.0 or less.
[0144] The above requirements Y2 to Y4 can be calculated in the same manner as above, except that the measurement target of the above requirement Y is changed and the peak position to be detected is changed. Similar to requirement Y, requirements Y2 to Y4 are peaks derived from the crystal structure of the specific boric acid compound, and it is presumed that when these peaks are not present, the specific boric acid compound has no specific crystal structure and is amorphous, and thus, as described above, a hydrated layer with excellent ion conductivity is easily formed. Also, similar to requirement Y, in requirements Y2 to Y4, even when specific peaks are present, the intensity ratio of any one of the specific peaks present being equal to or less than a predetermined value indicates that the specific boric acid compound has almost no crystal structure, and it is presumed that, as described above, a hydrated layer with excellent ion conductivity is easily formed.
[0145] In the above X-ray diffraction pattern of requirement Y2, if the peak top is located in the range of 15.4 to 15.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the first peak and the above requirement Y2 is judged. In addition, in the above X-ray diffraction pattern of requirement Y2, if the peak top is located in the range of 23.4 to 23.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the second peak and the above requirement Y2 is judged. In addition, in the above X-ray diffraction pattern of requirement Y2, if the peak top is located in the range of 26.8 to 27.2° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the third peak and the above requirement Y2 is judged. In addition, in the above X-ray diffraction pattern of requirement Y2, if the peak top is located in the range of 29.4 to 29.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the fourth peak and the above requirement Y2 is judged.
[0146] In the above X-ray diffraction pattern of requirement Y3, if the peak top is located in the range of 19.7 to 20.1° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the first peak and the above requirement Y3 is judged. In addition, in the above X-ray diffraction pattern of requirement Y3, if the peak top is located in the range of 22.3 to 22.7° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the second peak and the above requirement Y3 is judged. In addition, in the above X-ray diffraction pattern of requirement Y3, if the peak top is located in the range of 27.3 to 27.7° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the third peak and the above requirement Y3 is judged.
[0147] In the above X-ray diffraction pattern of requirement Y4, if the peak top is located in the range of 16.5 to 16.9° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the first peak and the above requirement Y4 is judged.
[0148] In terms of obtaining superior effects of the present invention, it is preferable that amorphous LiB3O5 satisfies the following requirement X2. The following requirement X2 is evaluated by the same procedure as the above requirement W, except that amorphous LiB3O5 is used as the measurement object, and the evaluation method is as described above. Requirement X2: In the reduced pair distribution function G(r) obtained from X-ray total scattering measurement of amorphous LiB3O5, there is a first peak whose peak top is located in the r range of 1.43±0.2 Å and a second peak whose peak top is located in the r range of 2.40±0.2 Å, and G(r) at the peak top of the first peak and G(r) at the peak top of the second peak exceed 1.0.
[0149] Amorphous Li3B 11 O 18 In order to obtain better effects of the present invention, it is preferable that the following requirement X3 is satisfied. The following requirement X3 is met when the measurement object is amorphous Li3B 11 O 18 Except for using the above, this requirement is evaluated using the same procedure as for requirement W described above, and the evaluation method is as described above. Requirement X3: Li3B in amorphous state 11 O 18 In the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement, there is a first peak whose peak top is located in the r range of 1.43±0.2 Å and a second peak whose peak top is located in the r range of 2.40±0.2 Å, and G(r) at the peak top of the first peak and G(r) at the peak top of the second peak are greater than 1.0.
[0150] Amorphous Li3B7O 12 In order to obtain better effects of the present invention, it is preferable that the following requirement X4 is satisfied. The following requirement X4 is met when the measurement object is amorphous Li3B7O 12 Except for using the above, this requirement is evaluated using the same procedure as for requirement W described above, and the evaluation method is as described above. Requirement X4: Li3B7O in amorphous state 12In the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement, there is a first peak whose peak top is located in the r range of 1.43±0.2 Å and a second peak whose peak top is located in the r range of 2.40±0.2 Å, and G(r) at the peak top of the first peak and G(r) at the peak top of the second peak are greater than 1.0.
[0151] In addition, in the requirements X2 to X4, as in the requirement X, the technical meaning is, as described above, that a periodic structure corresponding to the atomic distance of B (boron)-O (oxygen) and the atomic distance of B (boron)-B (boron) is present in the specific boric acid compound.
[0152] The method for producing the specific boric acid compound is not particularly limited. 11 O 18 or Li3BO 12 A method for producing the same includes subjecting the material to a mechanical milling treatment, which will be described later.
[0153] (water) A fifth embodiment of the lithium-based solid electrolyte of the present invention contains water. In the fifth embodiment of the lithium-based solid electrolyte of the present invention, the content of water is not particularly limited. In particular, in terms of the superior effect of the present invention, in the third embodiment of the lithium-based solid electrolyte of the present invention, the molar ratio of water to the specific boric acid compound (molar amount of water / molar amount of specific boric acid compound) is preferably 3 to 15, more preferably 4 to 13, further preferably 5 to 13, and particularly preferably 10 to 13.
[0154] (Lithium salts) A fifth embodiment of the lithium-based solid electrolyte of the present invention comprises a lithium salt. The type of lithium salt is not particularly limited, and examples thereof include the lithium salts exemplified in Step 1A described below, which will be described in detail later. In the fifth embodiment of the lithium-based solid electrolyte of the present invention, the content of the lithium salt is not particularly limited. In the fifth embodiment of the lithium-based solid electrolyte of the present invention, the mass ratio of the lithium salt content to the specific lithium tetraborate content (lithium salt content mass / specific boric acid compound content mass) is not particularly limited. In particular, in terms of the superior effect of the present invention, the molar ratio of the lithium salt to the specific boric acid compound (lithium salt molar amount / specific boric acid compound molar amount) in the fifth embodiment of the lithium-based solid electrolyte of the present invention is preferably 0.001 to 1.2, more preferably 0.01 to 1.2, further preferably 0.1 to 1.2, and particularly preferably 0.5 to 1.2.
[0155] When the fifth embodiment of the lithium-based solid electrolyte of the present invention contains amorphous LiB3O5, the fifth embodiment of the lithium-based solid electrolyte of the present invention preferably satisfies the following requirement Y5. Requirement Y5 is a requirement that is evaluated by the same procedure as requirement Y2, except that a lithium-based solid electrolyte is used as the measurement object. Requirement Y5: In an X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of a lithium-based solid electrolyte, none of the following peaks are present: a first peak having a peak top in the range of 15.4 to 15.8° and a full width at half maximum of 0.65° or less, a second peak having a peak top in the range of 23.4 to 23.8° and a full width at half maximum of 0.65° or less, a third peak having a peak top in the range of 26.8 to 27.2° and a full width at half maximum of 0.65° or less, and a fourth peak having a peak top in the range of 29.4 to 29.8° and a full width at half maximum of 0.65° or less; or, in the X-ray diffraction pattern, if at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: Calculate average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of a specific peak, calculate average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of a specific peak, calculate the arithmetic average of the average intensities 1 and 2, and define the ratio of the peak intensity at the peak top of the specific peak to the arithmetic average as the intensity ratio.
[0156] In particular, in the requirement Y5, in the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of the lithium-based solid electrolyte, it is preferable that the first peak, the second peak, the third peak, and the fourth peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, the intensity ratio of at least one of the specific peaks is 3.0 or less. In particular, it is more preferable that the first peak, the second peak, the third peak, and the fourth peak are not present, or when a specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak is present, the intensity ratio of at least one of the specific peaks is 2.0 or less.
[0157] In addition, the fifth embodiment of the lithium-based solid electrolyte of the present invention is Li3B in an amorphous state. 11 O 18 In this case, the fifth embodiment of the lithium-based solid electrolyte of the present invention preferably satisfies the following requirement Y6. Requirement Y6 is a requirement that is evaluated by the same procedure as requirement Y3, except that a lithium-based solid electrolyte is used as the measurement object. Requirement Y6: In an X-ray diffraction pattern obtained by X-ray diffraction measurement of a lithium-based solid electrolyte using CuKα radiation, none of the following is present: a first peak having a peak top in the range of 19.7 to 20.1° and a full width at half maximum of 0.65° or less, a second peak having a peak top in the range of 22.3 to 22.7° and a full width at half maximum of 0.65° or less, and a third peak having a peak top in the range of 27.3 to 27.7° and a full width at half maximum of 0.65° or less; or, in the X-ray diffraction pattern, if at least one specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, the intensity ratio of at least one of the specific peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: Calculate average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of a specific peak, calculate average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of a specific peak, calculate the arithmetic average of the average intensities 1 and 2, and define the ratio of the peak intensity at the peak top of the specific peak to the arithmetic average as the intensity ratio.
[0158] In particular, in requirement Y6, in an X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of a lithium-based solid electrolyte, if none of the first peak, the second peak, and the third peak are present, or if a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is preferable that the intensity ratio of at least one of the specific peaks is 3.0 or less. In particular, if none of the first peak, the second peak, and the third peak are present, or if a specific peak selected from the group consisting of the first peak, the second peak, and the third peak is present, it is more preferable that the intensity ratio of at least one of the specific peaks is 2.0 or less.
[0159] In addition, the fifth embodiment of the lithium-based solid electrolyte of the present invention is Li3B7O in an amorphous state. 12 In this case, the fifth embodiment of the lithium-based solid electrolyte of the present invention preferably satisfies the following requirement Y7. Requirement Y7 is a requirement that is evaluated by the same procedure as requirement Y4, except that a lithium-based solid electrolyte is used as the measurement object. Requirement Y7: In an X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation for a lithium-based solid electrolyte, the peak top is located in the range of 16.5 to 16.9°, and no first peak having a full width at half maximum of 0.65° or less is present, or, if a first peak is present in the X-ray diffraction pattern, the intensity ratio of at least one of the first peaks calculated by the following intensity measurement method is 5.0 or less. Intensity measurement method: Calculate average intensity 1 in the range of +0.45° to +0.55° from the diffraction angle 2θ of the peak top of a specific peak, calculate average intensity 2 in the range of -0.55° to -0.45° from the diffraction angle 2θ of the peak top of a specific peak, calculate the arithmetic average of the average intensities 1 and 2, and define the ratio of the peak intensity at the peak top of the specific peak to the arithmetic average as the intensity ratio.
[0160] In particular, in requirement Y7, in an X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of a lithium-based solid electrolyte, it is preferable that the first peak does not exist, or if the first peak exists, the intensity ratio of the first peak is 3.0 or less. In particular, it is more preferable that the first peak does not exist, or if the first peak exists, the intensity ratio of the first peak is 2.0 or less.
[0161] In the above X-ray diffraction pattern of requirement Y5, if the peak top is located in the range of 15.4 to 15.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the first peak and the above requirement Y5 is judged. In addition, in the above X-ray diffraction pattern of requirement Y5, if the peak top is located in the range of 23.4 to 23.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the second peak and the above requirement Y5 is judged. In addition, in the above X-ray diffraction pattern of requirement Y5, if the peak top is located in the range of 26.8 to 27.2° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the third peak and the above requirement Y5 is judged. In addition, in the above X-ray diffraction pattern of requirement Y5, if the peak top is located in the range of 29.4 to 29.8° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the fourth peak and the above requirement Y5 is judged.
[0162] In the above X-ray diffraction pattern of requirement Y6, if the peak top is located in the range of 19.7 to 20.1° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the first peak and the above requirement Y6 is judged. In addition, in the above X-ray diffraction pattern of requirement Y6, if the peak top is located in the range of 22.3 to 22.7° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the second peak and the above requirement Y6 is judged. In addition, in the above X-ray diffraction pattern of requirement Y6, if the peak top is located in the range of 27.3 to 27.7° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the third peak and the above requirement Y6 is judged.
[0163] In the above X-ray diffraction pattern of requirement Y7, if the peak top is located in the range of 16.5 to 16.9° and there are two or more peaks with a full width at half maximum of 0.65° or less, the peak with the greatest diffracted X-ray intensity is selected as the first peak and the above requirement Y7 is judged.
[0164] The fifth embodiment of the lithium-based solid electrolyte of the present invention preferably satisfies the following requirement X5, in terms of better effects of the present invention. The following requirement X5 is a requirement that is evaluated by the same procedure as the above-mentioned requirement W, except that the fifth embodiment of the lithium-based solid electrolyte of the present invention is used as the measurement object, and the evaluation method is as described above. Requirement X5: In the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement of the fifth embodiment of the lithium-based solid electrolyte, there is a first peak whose peak top is located in the range of r 1.43±0.2 Å, and a second peak whose peak top is located in the range of r 2.40±0.2 Å, and the G(r) at the peak top of the first peak and the G(r) at the peak top of the second peak are greater than 1.0.
[0165] <<Inorganic solid electrolyte>> <First embodiment> A first embodiment of the inorganic solid electrolyte of the present invention is an inorganic solid electrolyte having conductivity of ions of an element selected from metal elements belonging to Group 1 of the periodic table and elements belonging to Group 2 of the periodic table. Metal elements belonging to Group 1 of the periodic table are elements other than H (hydrogen element) among the elements exemplified as Group 1 elements of the periodic table, and include Li, Na, K, Rb, Cs, and Fr. Moreover, examples of Group 2 elements in the periodic table include Be, Mg, Ca, Sr, Ba, and Ra. In particular, the inorganic solid electrolyte preferably has Li ion conductivity.
[0166] A first embodiment of the inorganic solid electrolyte of the present invention contains an element selected from the group consisting of metal elements belonging to Group 1 of the periodic table and Group 2 of the periodic table (hereinafter, also simply referred to as "element X"), B, and O. Examples of the element X include those listed above, with Li being preferred.
[0167] The first embodiment of the inorganic solid electrolyte of the present invention further includes two or more specific elements selected from the group consisting of Group 3 elements of the periodic table, Group 4 elements of the periodic table, Group 13 elements of the periodic table, Group 14 elements of the periodic table, Group 15 elements of the periodic table, Group 16 elements of the periodic table, Group 17 elements of the periodic table, and H. The number of types of specific elements included in the first embodiment of the inorganic solid electrolyte of the present invention may be three or more. Among these, the number of types of specific elements included in the inorganic solid electrolyte is preferably 2 to 5, and more preferably 2 to 4, in terms of better effects of the present invention. Group 3 elements of the periodic table include Sc, Y, the lanthanides, and the actinides. Group 4 elements of the periodic table include Ti, Zr, Hf, and Rf. Group 13 elements of the periodic table include B, Al, Ga, In, Tl, and Nh. Group 14 elements of the periodic table include C, Si, Ge, Sn, Pb, and Fl. Group 15 elements of the periodic table include N, P, As, Sb, Bi, and Mc. Group 16 elements of the periodic table include O, S, Se, Te, Po, and Lv. Group 17 elements of the periodic table include F, Cl, Br, I, At, and Ts. The first embodiment of the inorganic solid electrolyte of the present invention preferably contains two or more specific elements selected from the group consisting of F, S, N, P, and C, more preferably contains two or more specific elements selected from the group consisting of F, S, C, and N, and further preferably contains three specific elements of F, S, and N.
[0168] In the first embodiment of the inorganic solid electrolyte of the present invention, when the molar amount of B in the inorganic solid electrolyte is taken as 4.00 and the molar amount of element X is expressed, the molar amount of element X is preferably 0.001 to 1000. In other words, when the molar amount of B contained is taken as 4.00, the relative value of the molar amount of element X contained is preferably 0.001 to 1000. Among these, in terms of superior effects of the present invention, when the molar amount of B in the lithium-based solid electrolyte is taken as 4.00 and the molar amount of element X is expressed, the molar amount of element X is preferably 0.1 to 10, more preferably 1.58 to 3.49, particularly preferably 1.58 to 3.00, more particularly preferably 1.90 to 3.00, and most preferably 2.00 to 3.00.
[0169] In the first embodiment of the inorganic solid electrolyte of the present invention, when the molar amount of B in the inorganic solid electrolyte is taken as 4.00 and the molar amount of O is expressed, the molar amount of O is preferably 0.001 to 1000. In other words, when the molar amount of B contained is taken as 4.00, the relative value of the molar amount of O contained is preferably 0.001 to 1000. Among these, in terms of superior effects of the present invention, when the molar amount of B in the inorganic solid electrolyte is taken as 4.00 and the molar amount of O is expressed, the molar amount of O is more preferably 0.1 to 100, further preferably 6.23 to 25.0, and particularly preferably 10.00 to 23.00.
[0170] In the first embodiment of the inorganic solid electrolyte of the present invention, when the molar amount of B in the inorganic solid electrolyte is taken as 4.00 and the molar amount of the specific element is expressed, the molar amount of each specific element is preferably 0.001 to 1000. In other words, when the molar amount of B contained is taken as 4.00, the relative value of the molar amount of each specific element contained is preferably 0.001 to 1000. In particular, in terms of superior effects of the present invention, when the molar amount of B in the inorganic solid electrolyte is taken as 4.00 and the molar amount of each specific element is expressed, the molar amount of each specific element is more preferably 0.001 to 100, further preferably 0.001 to 6.0, and particularly preferably 0.01 to 5.0. As described above, in the first embodiment of the inorganic solid electrolyte of the present invention, two or more specific elements are included. Therefore, for example, when the first embodiment of the inorganic solid electrolyte of the present invention includes two specific elements, a specific element A and a specific element B which is a different type of element from the specific element A, when the molar amount of B in the inorganic solid electrolyte is 4.00, the molar amount of the specific element A and the molar amount of the specific element B are each preferably 0.001 to 1000. Also, for example, when the first embodiment of the inorganic solid electrolyte of the present invention includes three specific elements, a specific element A, a specific element B which is a different type of element from the specific element A, and a specific element C which is a different type of element from the specific elements A and B, when the molar amount of B in the inorganic solid electrolyte is 4.00, the molar amount of the specific element A, the molar amount of the specific element B, and the molar amount of the specific element C are each preferably 0.001 to 1000.
[0171] The contents of the element X, B, and the specific element in the first embodiment of the inorganic solid electrolyte of the present invention are determined by known elemental analysis. The first embodiment of the inorganic solid electrolyte of the present invention may contain elements other than the elements X, B, O, and the specific element.
[0172] A first embodiment of the inorganic solid electrolyte of the present invention is amorphous. It is presumed that the first embodiment of the inorganic solid electrolyte of the present invention is amorphous and satisfies the requirement R described below, so that a soft hydration layer is easily formed on the surface side of the inorganic solid electrolyte, and the presence of this hydration layer results in good ionic conductivity.
[0173] The first embodiment of the inorganic solid electrolyte of the present invention satisfies the following requirement R. Note that requirement R is evaluated by the same procedure as requirement Z of the fourth embodiment of the lithium-based solid electrolyte of the present invention, except that the first embodiment of the inorganic solid electrolyte is used as the measurement target of requirement Z, and the evaluation method is as described above. When requirement R is satisfied, it indicates that the inorganic solid electrolyte contains a large number of OH groups and a large amount of water, as with requirement Z described above. Requirement R: In the infrared absorption spectrum of the inorganic solid electrolyte, 800 to 1600 cm -1 The maximum absorption intensity in the wavenumber region of 3000 to 3500 cm -1 The ratio of the maximum absorption intensity in the wave number region of is 1 / 5 or more.
[0174] <Second embodiment> A second embodiment of the inorganic solid electrolyte of the present invention comprises a compound containing an element selected from the group consisting of metal elements belonging to Group 1 of the periodic table and elements of Group 2 of the periodic table (corresponding to the above-mentioned element X), B, and O, water, and a salt containing an element selected from the group consisting of metal elements belonging to Group 1 of the periodic table and elements of Group 2 of the periodic table.
[0175] (Compounds containing elements X, B, and O (hereinafter simply referred to as "compounds containing element X") A second embodiment of the inorganic solid electrolyte of the present invention comprises a compound containing the elements X, B, and O. Examples of the element X are as explained in the first embodiment of the inorganic solid electrolyte above, and Li is preferable. When the element X is Li, the above compound includes, for example, Li2B4O7, LiB3O5, LiBO5, Li3B 11 O 18 , and Li2B7O 12Examples include: The compound is preferably amorphous.
[0176] (water) A second embodiment of the inorganic solid electrolyte of the present invention contains water. In the second embodiment of the inorganic solid electrolyte of the present invention, the content of water is not particularly limited. In particular, in terms of more excellent effects of the present invention, the molar ratio of water to the element X-containing compound (molar amount of water / molar amount of element X-containing compound) in the second embodiment of the inorganic solid electrolyte of the present invention is preferably 3 to 15, more preferably 4 to 13, further preferably 5 to 13, and particularly preferably 10 to 13.
[0177] (Salt containing an element selected from the group consisting of metal elements belonging to Group 1 of the periodic table and elements belonging to Group 2 of the periodic table) A second embodiment of the inorganic solid electrolyte of the present invention includes a salt containing an element (corresponding to the above-mentioned element X) selected from the group consisting of metal elements belonging to Group 1 of the periodic table and elements of Group 2 of the periodic table (hereinafter, also simply referred to as "element X-containing salt"). The salt containing element X is not particularly limited as long as it is a salt containing element X. For example, when element X is Li, the salt containing element X corresponds to a lithium salt, and when element X is Na, the salt containing element X corresponds to a sodium salt. In the salt containing element X, it is usually composed of a cation of element X and an anion. The structure of the anion is not particularly limited, and includes known anions, and an organic anion is preferable. As the organic ion, an organic anion having a fluorine atom is preferable. The salt containing element X preferably contains two or more specific elements selected from the group consisting of Group 3 elements in the periodic table, Group 4 elements in the periodic table, Group 13 elements in the periodic table, Group 14 elements in the periodic table, Group 15 elements in the periodic table, Group 16 elements in the periodic table, Group 17 elements in the periodic table, and H.
[0178] In the second embodiment of the inorganic solid electrolyte of the present invention, the mass ratio of the content of the element X-containing salt to the content of the above-mentioned element X-containing compound (mass content of element X-containing salt / mass content of element X-containing compound) is not particularly limited. In particular, in terms of better effects of the present invention, the molar ratio of the element X-containing salt to the element X-containing compound (molar amount of element X-containing salt / molar amount of element X-containing compound) in the second embodiment of the inorganic solid electrolyte of the present invention is preferably 0.001 to 1.5, more preferably 0.001 to 1.2, further preferably 0.01 to 1.2, particularly preferably 0.1 to 1.2, and most preferably 0.5 to 1.2.
[0179] <Method of manufacturing lithium-based solid electrolyte> The method for producing the lithium-based solid electrolyte of the present invention (first embodiment to fourth embodiment) is not particularly limited, but a production method including the following steps 1A to 3A is preferred from the viewpoint of producing the lithium-based solid electrolyte of the present invention with good productivity. Step 1A: A step of subjecting a lithium-based oxide containing Li and B to a mechanical milling treatment in the presence of a specific element source. Step 2A: mixing the product obtained in step 1A with water Step 3A: A step of removing water from the dispersion obtained in step 2A to obtain a lithium-based solid electrolyte. The steps of the above manufacturing method will be described in detail below.
[0180] Step 1A is a step of subjecting a lithium-based oxide containing Li and B to a mechanical milling treatment in the presence of a specific element source. Below, the materials used in this step 1A are described in detail, followed by a detailed description of the procedure.
[0181] The specific element source contains two or more elements selected from the group consisting of Group 4 elements of the periodic table, Group 15 elements of the periodic table, Group 16 elements of the periodic table, Group 17 elements of the periodic table, Si, C, Sc, Y, and H, and preferably contains two or more elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N. The specific element source only needs to contain two or more elements from among the above-mentioned elements, and may be composed of one type of compound or two or more types of compounds. For example, the specific element source may be composed of a compound containing two or more elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N, or may be composed of compound 1 containing at least one element selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N, and compound 2 containing an element selected from the above group that is different from the element contained in compound 1. The specific element source preferably contains two to four elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N, and more preferably contains three elements.
[0182] The compound contained in the specific element source is preferably a salt, and more preferably a lithium salt (particularly, a lithium imide salt). The lithium salt is preferably a compound represented by formula (1). Equation (1) LiN(R f1 SO2)(R f2 SO2) R f1 and R f2 each independently represents a halogen atom or a perfluoroalkyl group. R f1 and R f2 When is a perfluoroalkyl group, the number of carbon atoms in the perfluoroalkyl group is not particularly limited. Rf1 and R f2 is preferably a halogen atom or a perfluoroalkyl group having 1 to 6 carbon atoms, more preferably a halogen atom or a perfluoroalkyl group having 1 to 2 carbon atoms, and even more preferably a halogen atom. When the volume of the terminal group increases, steric hindrance increases, which becomes a factor that inhibits ion conduction, so R f1 and R f2 When is a perfluoroalkyl group, it is preferable that the number of carbon atoms is small.
[0183] Examples of compounds contained in the specific element source are given below. Among the compounds given below, a compound containing only one specific element is used together with another compound containing at least one other specific element, so that the specific element source contains two or more specific elements, as described above. (L-1) Inorganic lithium salts: inorganic fluoride salts such as LiPF6, LiBF4, LiAsF6, and LiSbF6; perhalogenates such as LiClO4, LiBrO4, and LiIO4; inorganic chloride salts such as LiAlCl4. (L-2) Fluorine-containing organic lithium salts: perfluoroalkanesulfonates such as LiCF3SO3; perfluoroalkanesulfonylimide salts such as LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(FSO2)2, and LiN(CF3SO2)(C4F9SO2); perfluoroalkanesulfonylmethide salts such as LiC(CF3SO2)3; fluoroalkyl fluorophosphates such as Li[PF5(CF2CF2CF3)], Li[PF4(CF2CF2CF3)2], Li[PF3(CF2CF2CF3)3], Li[PF5(CF2CF2CF2CF3)], Li[PF4(CF2CF2CF2CF3)2], and Li[PF3(CF2CF2CF2CF3)3]. (L-3) Oxalatoborate salts: lithium bis(oxalato)borate and lithium difluorooxalatoborate. In addition to the above, other examples include LiF, LiCl, LiBr, LiI, Li2SO4, LiNO3, Li2CO3, CH3COOLi, LiAsF6, LiSbF6, LiAlCl4, and LiB(C6H5)4. Among them, LiPF6, LiBF4, LiAsF6, LiSbF6, LiClO4, Li(R f1 SO3), LiN(R f1 SO2)2, LiN(FSO2)2, or LiN(R f1 SO2)(R f2 SO2) is preferred, LiPF6, LiBF4, LiN(R f1 SO2)2, LiN(FSO2)2, or LiN(R f1 SO2)(R f2 SO2) is more preferred. Here, R f1 and R f2 each independently represents a perfluoroalkyl group.
[0184] The amount of the specific element source used is not particularly limited, and is appropriately adjusted so as to obtain the above-mentioned lithium-based solid electrolyte of the present invention. In particular, the amount of the specific element source used is preferably 1 to 300 parts by mass, and more preferably 100 to 200 parts by mass, per 100 parts by mass of the lithium-based oxide containing Li and B.
[0185] Lithium oxides containing Li and B include Li2B4O7, LiBO5, LiB3O5, and Li3B 11 O 18 , Li2B7O 12 , LiB2O3(OH)H2O, and Li4B8O 13 (OH)2(H2O)3, etc.
[0186] Mechanical milling is a process in which a sample is pulverized while applying mechanical energy. Examples of the mechanical milling treatment include a ball mill, a vibration mill, a turbo mill, and a disk mill, and the ball mill is preferred because it can produce the lithium-based solid electrolyte of the present invention with good productivity. Examples of the ball mill include a vibration ball mill, a rotary ball mill, and a planetary ball mill, and the planetary ball mill is more preferred.
[0187] The optimum conditions for the ball mill treatment are selected depending on the raw material used. The material of the grinding balls (media) used in the ball mill is not particularly limited, but examples thereof include agate, silicon nitride, stabilized zirconia (YSZ), alumina, and iron-based alloys. From the viewpoint of enabling the lithium-based solid electrolyte of the present invention to be produced with good productivity, stabilized zirconia (YSZ) is preferred. The average particle size of the grinding balls is not particularly limited, but is preferably 1 to 10 mm, more preferably 3 to 7 mm, from the viewpoint of manufacturing the lithium-based solid electrolyte of the present invention with good productivity. The average particle size is obtained by measuring the diameters of 50 random grinding balls and calculating the average. When the grinding balls are not spherical, the major axis is taken as the diameter. The number of grinding balls used in the ball mill is not particularly limited, but is preferably 10 to 100, more preferably 40 to 60, from the viewpoint of producing the lithium-based solid electrolyte of the present invention with good productivity.
[0188] The material of the grinding pot used in the ball mill is not particularly limited, but examples thereof include agate, silicon nitride, stabilized zirconia (YSZ), alumina, and iron-based alloys. From the viewpoint of enabling the lithium-based solid electrolyte of the present invention to be produced with good productivity, stabilized zirconia (YSZ) is preferred.
[0189] The rotation speed when the ball mill is used is not particularly limited, but from the viewpoint of producing the lithium-based solid electrolyte of the present invention with good productivity, it is preferably 200 to 700 rpm, and more preferably 350 to 550 rpm. The treatment time in the ball mill is not particularly limited, but from the viewpoint of producing the lithium-based solid electrolyte of the present invention with good productivity, it is preferably 10 to 200 hours, and more preferably 20 to 140 hours. The atmosphere during ball milling may be air or an inert gas (eg, argon, helium, and nitrogen) atmosphere.
[0190] Step 2A is a step of mixing the product obtained in step 1A with water. By carrying out this step, the lithium-based oxide containing Li and B that has been subjected to mechanical milling treatment and obtained in step 1A is mixed with water, and the lithium-based solid electrolyte of the present invention containing a large amount of O (oxygen element) is produced. The amount of water used is not particularly limited, but in terms of better effects of the present invention, the amount of water used is preferably 10 to 200 parts by mass, and more preferably 50 to 150 parts by mass, per 100 parts by mass of the product obtained in step 1A.
[0191] The method for mixing the product obtained in step 1A with water is not particularly limited, and they may be mixed all at once, or water may be added stepwise to the product obtained in step 1A and mixed. During mixing, ultrasonic treatment may be performed as necessary. The ultrasonic treatment time is not particularly limited, but is preferably from 10 minutes to 5 hours in terms of obtaining a better effect of the present invention.
[0192] Step 3A is a step of removing water from the dispersion liquid obtained in step 2A to obtain a lithium-based solid electrolyte. The method for removing water from the dispersion obtained in step 2A is not particularly limited, and water may be removed by a heat treatment or a vacuum drying treatment.
[0193] Before the above step 1A, a step 0 may be carried out in which a lithium-based oxide containing Li and B is subjected to mechanical milling treatment in an environment in which a specific element source is not present. A preferred embodiment of the mechanical milling treatment carried out in step 0 is the same as the preferred embodiment of the mechanical milling treatment carried out in step 1A described above.
[0194] Another preferred embodiment of the method for producing a lithium-based solid electrolyte of the present invention is a production method including the following steps 1B to 3B. Step 1B: A step of subjecting a lithium-based oxide containing Li and B to mechanical milling treatment. Step 2B: mixing the product obtained in step 1B with water and a source of a specific element. Step 3B: A step of removing water from the dispersion obtained in step 2B to obtain a lithium-based solid electrolyte. The difference between step 1B and step 1A is that in step 1A, mechanical milling is carried out in the presence of a specific element source, whereas in step 1B, mechanical milling is carried out without using a specific element source. A preferred embodiment of the mechanical milling treatment carried out in step 1B is the same as the preferred embodiment of the mechanical milling treatment carried out in step 1A.
[0195] The difference between step 2B and step 2A is that in step 2B, the product obtained in step 1B is mixed with water and a source of the specific element. The specific element source used in step 2B is the same as the specific element source used in step 1A. The amount of the specific element source used in step 2B is preferably 1 to 300 parts by mass, and more preferably 100 to 200 parts by mass, relative to 100 parts by mass of the product obtained in step 1B. The procedure of step 2B is not particularly limited, and may be a method of mixing the product obtained in step 1B, water, and a specific element source all at once (method 1), a method of mixing the product obtained in step 1B with water to prepare a solution, and then mixing the obtained solution with a specific element source (method 2), or a method of mixing the product obtained in step 1B with water to prepare solution 1, mixing the specific element source with water to prepare solution 2, and mixing solution 1 and solution 2 (method 3). When mixing the product obtained in step 1B with water, a dispersion treatment such as ultrasonic treatment may be appropriately performed. Among these, method 3 is preferred since it provides a more excellent effect of the present invention. In method 2, when the product obtained in step 1B is mixed with water to mix the solution and the specific element source, if the amount of the specific element source is too large, the resulting solution is likely to gel, making it difficult to increase the amount of the specific element source mixed in. In contrast, in method 3, even if the product obtained in step 1B and the specific element source are mixed in approximately equimolar amounts, the solution is unlikely to gel, making it easy to increase the amount of the specific element source mixed in.
[0196] The procedure of step 3B is the same as that of step 3A.
[0197] Another preferred embodiment of the method for producing a lithium-based solid electrolyte of the present invention is a production method including the following steps 1C to 3C. Step 1C: A step of subjecting a lithium-based oxide containing Li and B to mechanical milling treatment. Step 2C: Mixing the product obtained in step 1C with water. Step 3C: A step of removing water from the dispersion obtained in step 2C and mixing the product obtained with a specific element source to obtain a lithium-based solid electrolyte. The procedure of step 1C is the same as that of step 1B. The procedure of step 2C is the same as that of step 2A. The difference between step 3C and step 3A is that the product obtained by removing water from the dispersion obtained in step 2C is mixed with a specific element source. The specific element source used in step 3C is the same as the specific element source used in step 1A. The amount of the specific element source used in step 3C is preferably 1 to 300 parts by mass, more preferably 100 to 200 parts by mass, per 100 parts by mass of the product obtained by removing water from the dispersion obtained in step 2C. The method for mixing the product obtained by removing water from the dispersion obtained in step 2C with the specific element source is not particularly limited, and may be a method in which the above product is impregnated with a solution in which the specific element source is dissolved in water, and the two are mixed.
[0198] That is, a preferred embodiment of the method for producing a lithium-based solid electrolyte of the present invention is as follows: A step 1 of subjecting a lithium-based oxide containing Li and B to a mechanical milling treatment; Step 2 is mixing the product obtained in step 1 with water; and step 3 of removing water from the dispersion obtained in step 2 to obtain a lithium-based solid electrolyte. The production method satisfies any one of the following requirements 1 to 3. Requirement 1: The mechanical milling treatment in step 1 is carried out in the presence of a specific element source. Requirement 2: In step 2, the product, water, and a source of the specific element are mixed. Requirement 3: In step 3, a product obtained by removing water from the dispersion liquid obtained in step 2 is mixed with a specific element source to obtain a lithium-based solid electrolyte.
[0199] In the above, an embodiment using a specific element source containing two or more elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N has been described, but the method for producing a lithium-based solid electrolyte of the present invention is not limited to this embodiment. For example, the fourth embodiment of the lithium-based solid electrolyte of the present invention described above may contain one or more elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N. In order to contain such one or more elements, an element source containing one or more elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N may be used as the specific element source.
[0200] <Method of manufacturing inorganic solid electrolyte> The method for producing the inorganic solid electrolyte of the present invention (first embodiment and second embodiment) is not particularly limited, and any known method can be used. Among them, it is preferable to produce the lithium-based solid electrolyte by the same procedure as the above-mentioned method for producing the lithium-based solid electrolyte of the present invention, except that an oxide containing elements X and B is used instead of the lithium-based oxide containing Li and B, and an element X-containing salt is used instead of the specific element source.
[0201] <Dispersion> The dispersion of the present invention contains the above-mentioned lithium-based solid electrolyte or inorganic solid electrolyte of the present invention and a solvent (e.g., organic solvent, water). The dispersion of the present invention is liquid, can be applied to various substrates, and is useful for producing a solid electrolyte layer. The content of the lithium-based solid electrolyte or inorganic solid electrolyte in the dispersion of the present invention is not particularly limited, but is preferably 5 to 80 mass %, more preferably 30 to 70 mass %, based on the total mass of the dispersion. The content of the solvent in the dispersion of the present invention is not particularly limited, but is preferably from 20 to 95% by mass, more preferably from 30 to 70% by mass, based on the total mass of the dispersion.
[0202] The dispersion of the present invention may contain other components in addition to the lithium-based solid electrolyte or inorganic solid electrolyte of the present invention and the solvent. Other components include a binder. Examples of the binder include various organic polymers. The organic polymer compound constituting the binder may be in a particulate or non-particulate form.
[0203] The other components include solid electrolytes other than the lithium-based solid electrolyte or inorganic solid electrolyte of the present invention. The other solid electrolyte means a solid electrolyte capable of moving ions therein. The solid electrolyte is preferably an inorganic solid electrolyte. Other solid electrolytes include sulfide-based inorganic solid electrolytes, oxide-based inorganic solid electrolytes, halide-based inorganic solid electrolytes, and hydride-based solid electrolytes.
[0204] The method for producing the dispersion of the present invention is not particularly limited, and examples thereof include a production method having the above-mentioned steps 1A and 2A, and a production method having steps 1B and 2B.
[0205] <Application> The lithium-based solid electrolyte and inorganic solid electrolyte of the present invention exhibit excellent ion conductivity and can be applied to various applications. The lithium-based solid electrolyte and inorganic solid electrolyte of the present invention can be used, for example, in various batteries (e.g., all-solid-state secondary batteries, solid oxide fuel cells, solid oxide steam electrolysis). In particular, the lithium-based solid electrolyte of the present invention is preferably used in all-solid-state lithium ion secondary batteries. More specifically, the lithium-based solid electrolyte and inorganic solid electrolyte of the present invention are preferably used to form the solid electrolyte contained in the positive electrode active material layer, solid electrolyte layer, and negative electrode active material layer in an all-solid-state secondary battery. In particular, the lithium-based solid electrolyte of the present invention is preferably used to form the solid electrolyte contained in the positive electrode active material layer, solid electrolyte layer, and negative electrode active material layer in an all-solid-state lithium ion secondary battery. In addition, the lithium-based solid electrolyte of the present invention is preferably used as the solid electrolyte contained in any of the positive electrode active material layer, solid electrolyte layer, and negative electrode active material layer in an all-solid-state lithium ion secondary battery. The lithium-based solid electrolyte and inorganic solid electrolyte of the present invention are also suitable for use as a coating material for coating the surface of a positive electrode active material. That is, one preferred embodiment of the present invention is a modified positive electrode active material having a positive electrode active material and a coating layer disposed on the positive electrode active material, the coating layer including the lithium-based solid electrolyte or inorganic solid electrolyte of the present invention. Furthermore, the lithium-based solid electrolyte and inorganic solid electrolyte of the present invention are preferably used as a coating material for coating the surface of a negative electrode active material. That is, one preferred embodiment of the present invention is a modified negative electrode active material having a negative electrode active material and a coating layer disposed on the negative electrode active material, the coating layer including the lithium-based solid electrolyte or inorganic solid electrolyte of the present invention.
[0206] When using the lithium-based solid electrolyte and inorganic solid electrolyte of the present invention, it is preferable to subject the lithium-based solid electrolyte and inorganic solid electrolyte of the present invention to a pressure treatment and mold them into a predetermined shape before use. The method of pressure treatment is not particularly limited, and examples thereof include a method using a known press device. The pressure applied during the pressure treatment is not particularly limited and an optimum pressure may be appropriately selected. In terms of obtaining superior effects of the present invention, the pressure is preferably 5 to 1500 MPa, and more preferably 10 to 600 MPa. The time for the pressure treatment is not particularly limited, but from the viewpoint of obtaining a superior effect of the present invention and of productivity, the time is preferably from 1 second to 0.5 hours, and more preferably from 2 seconds to 0.2 hours. A heat treatment may be carried out during the pressure treatment. The heating temperature during the heat treatment is not particularly limited, but is preferably 40 to 400° C., more preferably 50 to 350° C. The heating time during the heat treatment is preferably 1 minute to 6 hours. The atmosphere during pressurization is not particularly limited, and examples thereof include air, dry air (dew point of -20°C or lower), and an inert gas (eg, argon, helium, and nitrogen) atmosphere.
[0207] The ionic conductivity (27° C.) of the lithium-based solid electrolyte and inorganic solid electrolyte of the present invention is not particularly limited. However, from the viewpoint of application to various uses, it is preferably 1.0×10 -5 S / cm or more is preferable, and 1.0×10 -4 The upper limit is not particularly limited, but is preferably 1.0×10 -2 It is often below S / cm.
[0208] The dispersion of the present invention containing the lithium-based solid electrolyte or inorganic solid electrolyte of the present invention can be suitably used as a dispersion for forming a solid electrolyte layer. The method for forming the solid electrolyte layer using the above-mentioned dispersion for forming a solid electrolyte layer is not particularly limited, and includes a method for forming a solid electrolyte layer by applying the dispersion for forming a solid electrolyte layer. If necessary, the formed coating film may be subjected to a pressure treatment.
[0209] The method for applying the solid electrolyte layer forming dispersion is not particularly limited, and examples thereof include spray application, spin coating, dip coating, slit coating, stripe coating, aerosol deposition method, thermal spraying, and bar coating. After applying the solid electrolyte layer forming dispersion, the obtained coating film may be subjected to a drying treatment as necessary. The drying temperature is not particularly limited, but the lower limit is preferably 30° C. or higher, more preferably 60° C. or higher, and even more preferably 80° C. or higher. The upper limit of the drying temperature is preferably 300° C. or lower, and more preferably 250° C. or lower.
[0210] The method for applying pressure to the coating film is not particularly limited, but examples include a method using a known press device (for example, a hydraulic cylinder press). The pressure applied during the pressure treatment is not particularly limited, but is preferably 5 to 1500 MPa, and more preferably 300 to 600 MPa, in that the ion conductivity of the formed solid electrolyte layer is superior. The time for the pressure treatment is not particularly limited, but is preferably 1 minute to 6 hours, more preferably 1 to 20 minutes, in terms of better ion conductivity of the solid electrolyte layer formed and productivity. A heat treatment may be carried out during the pressure treatment. The heating temperature during the heat treatment is not particularly limited, but is preferably 30 to 300° C., and the heating time is more preferably 1 minute to 6 hours. The atmosphere during pressurization is not particularly limited, and examples thereof include air, dry air (dew point of -20°C or lower), and an inert gas (eg, argon, helium, and nitrogen) atmosphere.
[0211] The lithium-based solid electrolyte and inorganic solid electrolyte of the present invention are also preferably used as components of an electrode-forming composition. That is, the electrode-forming composition of the present invention contains the above-mentioned lithium-based solid electrolyte of the present invention. The electrode-forming composition of the present invention contains the above-mentioned lithium-based solid electrolyte or inorganic solid electrolyte of the present invention, and an active material. The mixing ratio of the lithium-based solid electrolyte or inorganic solid electrolyte to the active material in the electrode-forming composition is not particularly limited, and the content ratio of the lithium-based solid electrolyte or inorganic solid electrolyte to the active material (mass of lithium-based solid electrolyte or inorganic solid electrolyte / mass of active material) is not particularly limited, but is preferably 0.01 to 50, more preferably 0.05 to 20.
[0212] The lithium-based solid electrolyte and the inorganic solid electrolyte contained in the electrode-forming composition are as described above. The active material includes a negative electrode active material and a positive electrode active material. The active material will be described in detail below.
[0213] (Negative electrode active material) The negative electrode active material is preferably one that can reversibly insert and release lithium ions. The negative electrode active material is not particularly limited, and examples thereof include carbonaceous materials, oxides of metals or semimetal elements, lithium alone, lithium alloys, and negative electrode active materials that can form alloys with lithium.
[0214] The carbonaceous material used as the negative electrode active material is a material that is substantially made of carbon. Examples of the carbonaceous material include petroleum pitch, carbon black such as acetylene black (AB), graphite (natural graphite and artificial graphite such as vapor-grown graphite), and carbonaceous materials obtained by baking various synthetic resins such as PAN (polyacrylonitrile)-based resins and furfuryl alcohol resins. Further examples include various carbon fibers such as PAN-based carbon fibers, cellulose-based carbon fibers, pitch-based carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol)-based carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers, mesophase microspheres, graphite whiskers, and plate-like graphite. These carbonaceous materials can be divided into non-graphitizable carbonaceous materials (also called hard carbon) and graphite-based carbonaceous materials depending on the degree of graphitization. The carbonaceous material preferably has the interplanar spacing, density, or crystallite size described in JP-A-62-022066, JP-A-2-006856, and JP-A-3-045473. The carbonaceous material does not need to be a single material, and a mixture of natural graphite and artificial graphite described in JP-A-5-090844 and graphite having a coating layer described in JP-A-6-004516 can also be used. The carbonaceous material is preferably hard carbon or graphite, and more preferably graphite.
[0215] The oxide of a metal element or a metalloid element used as the negative electrode active material is not particularly limited as long as it is an oxide capable of absorbing and releasing lithium, and examples thereof include an oxide of a metal element (metal oxide), a composite oxide of a metal element, a composite oxide of a metal element and a metalloid element, and an oxide of a metalloid element (metalloid oxide). The composite oxide of a metal element and the composite oxide of a metal element and a metalloid element are collectively called a metal composite oxide. As these oxides, amorphous oxides are preferred, and chalcogenides which are reaction products of metal elements and elements of Group 16 of the periodic table are also preferred. In the present invention, the metalloid element refers to an element that exhibits intermediate properties between metallic elements and non-metalloid elements, and generally includes six elements, namely, boron, silicon, germanium, arsenic, antimony, and tellurium, and further includes three elements, namely, selenium, polonium, and astatine. Moreover, the term "amorphous" means that the material has a broad scattering band having a peak in the region of 20 to 40° in 2θ values in an X-ray diffraction method using CuKα radiation, and may have crystalline diffraction lines. The strongest intensity of the crystalline diffraction lines seen in the region of 40 to 70° in 2θ values is preferably 100 times or less, more preferably 5 times or less, of the diffraction line intensity of the peak of the broad scattering band seen in the region of 20 to 40° in 2θ values, and further preferably has no crystalline diffraction lines.
[0216] Among the compound group consisting of the above-mentioned amorphous oxides and chalcogenides, amorphous oxides or the above-mentioned chalcogenides of metalloid elements are more preferred, and (composite) oxides or chalcogenides consisting of one or a combination of two or more elements selected from the elements of Groups 13 (IIIB) to 15 (VB) of the periodic table (e.g., Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi) are even more preferred. As amorphous oxides and chalcogenides, Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3 or Sb2S5 are preferred. As a negative electrode active material that can be used in combination with the amorphous oxide negative electrode active material mainly composed of Sn, Si, or Ge, a carbonaceous material capable of absorbing and / or releasing lithium ions or lithium metal, lithium alone, a lithium alloy, or a negative electrode active material that can be alloyed with lithium is preferable.
[0217] The oxides of metal elements or metalloid elements (particularly metal (composite) oxides) and the above chalcogenides preferably contain at least one of titanium and lithium as a constituent component in terms of high current density charge / discharge characteristics. Examples of the metal composite oxide containing lithium (lithium composite metal oxide) include composite oxides of lithium oxide and the above metal oxides, the above metal composite oxides, or the above chalcogenides. More specifically, Li2SnO2 is included. The negative electrode active material (e.g., metal oxide) preferably contains titanium element (titanium oxide). Specifically, Li4Ti5O 12 (Lithium titanate [LTO]) is preferable because it has excellent rapid charge / discharge characteristics due to its small volumetric change when absorbing and releasing lithium ions, and because it can suppress electrode deterioration and improve the life of all-solid-state lithium ion secondary batteries.
[0218] The lithium alloy as the negative electrode active material is not particularly limited as long as it is an alloy commonly used as the negative electrode active material of an all-solid-state lithium-ion secondary battery. For example, a lithium aluminum alloy can be mentioned.
[0219] The negative electrode active material capable of forming an alloy with lithium is not particularly limited as long as it is commonly used as the negative electrode active material of an all-solid-state lithium-ion secondary battery. Examples of the above negative electrode active material include a negative electrode active material (alloy) containing a silicon element or a tin element, and each metal such as Al and In. A negative electrode active material containing a silicon element (silicon element-containing active material) that enables a higher battery capacity is preferable, and a silicon element-containing active material in which the content of the silicon element is 50 mol% or more of all constituent elements is more preferable. Generally, a negative electrode containing these negative electrode active materials (for example, a Si negative electrode containing a silicon element-containing active material, a Sn negative electrode containing an active material containing a tin element) can occlude more Li ions than a carbon negative electrode (such as graphite and acetylene black). That is, the amount of Li ions occluded per unit mass increases. Therefore, the battery capacity can be increased. As a result, there is an advantage that the battery driving time can be extended.
[0220] Examples of the silicon element-containing active material include silicon materials such as Si and SiOx (0 < x ≤ 1), and further, silicon-containing alloys containing titanium, vanadium, chromium, manganese, nickel, copper, or lanthanum (for example, LaSi2, VSi2, La-Si, Gd-Si, and Ni-Si), or organized active materials (for example, LaSi2 / Si). In addition, active materials containing a silicon element and a tin element such as SnSiO3 and SnSiS3 can be mentioned. Note that SiOx can be used as the negative electrode active material (semi-metal oxide) itself, and can also be used as a negative electrode active material (its precursor material) capable of alloying with lithium because Si is generated by the operation of an all-solid-state lithium-ion secondary battery. Examples of the negative electrode active material having a tin element include Sn, SnO, SnO2, SnS, SnS2, and the above active materials containing a silicon element and a tin element.
[0221] In terms of battery capacity, the negative electrode active material is preferably an negative electrode active material that can be alloyed with lithium, more preferably the above-mentioned silicon material or a silicon-containing alloy (an alloy containing silicon element), and further preferably silicon (Si) or a silicon-containing alloy.
[0222] The shape of the negative electrode active material is not particularly limited, but is preferably particulate. The volume average particle size of the negative electrode active material is not particularly limited, but is preferably 0.1 to 60 μm, more preferably 0.5 to 20 μm, and even more preferably 1.0 to 15 μm. The volume average particle size is measured by the following procedure. The negative electrode active material is diluted in water (heptane if the material is unstable in water) to prepare a 1% by mass dispersion in a 20 mL sample bottle. The diluted dispersion sample is irradiated with 1 kHz ultrasound for 10 minutes and used for testing immediately afterwards. Using this dispersion sample, data is collected 50 times using a quartz measurement cell at a temperature of 25°C using a laser diffraction / scattering type particle size distribution analyzer to obtain the volume average particle size. For other detailed conditions, refer to the description in JIS Z 8828:2013 "Particle size analysis - Dynamic light scattering method" as necessary. Five samples are prepared for each level and the average value is used.
[0223] The negative electrode active material may be used alone or in combination of two or more kinds.
[0224] The surface of the negative electrode active material may be coated with another metal oxide. Examples of the surface coating agent include metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si, or Li. Specific examples include titanate spinel, tantalum-based oxides, niobium-based oxides, and lithium niobate-based compounds, such as Li4Ti5O 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, and B2O3. The surface of the electrode containing the negative electrode active material may be surface-treated with sulfur or phosphorus. Furthermore, the particle surfaces of the negative electrode active material may be subjected to a surface treatment with active rays or active gas (eg, plasma) before or after the above-mentioned surface coating.
[0225] (Cathode active material) The positive electrode active material is preferably one that can reversibly insert and / or release lithium ions. The positive electrode active material is not particularly limited, and is preferably a transition metal oxide, and more preferably a transition metal element M a It is more preferable that the transition metal oxide contains an element M (one or more elements selected from Co, Ni, Fe, Mn, Cu and V). b (Elements of Group 1 (Ia) of the periodic table of metals other than lithium, elements of Group 2 (IIa), Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, B, etc.) may be mixed. The amount of the mixed element is as follows: a The amount of Li / M is preferably 0 to 30 mol%. a More preferably, the above-mentioned compounds are synthesized by mixing them so that the molar ratio is 0.3 to 2.2. Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock-salt structure, (MB) transition metal oxides having a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halide phosphate compounds, and (ME) lithium-containing transition metal silicate compounds. Among these, (MA) transition metal oxides having a layered rock-salt structure are preferred, and LiCoO2 or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 is more preferred.
[0226] (MA) Transition metal oxides having a layered rock salt structure include, for example, LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (Lithium Nickel Cobalt Aluminum Oxide [NCA]), LiNi1 / 3 Co 1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide). (MB) Examples of transition metal oxides having a spinel structure include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8, and Li2NiMn3O8. (MC) Examples of lithium-containing transition metal phosphate compounds include olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, iron pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphates such as Li3V2(PO4)3 (lithium vanadium phosphate). (MD) Examples of lithium-containing transition metal halophosphate compounds include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F. (ME) Examples of lithium-containing transition metal silicate compounds include Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4.
[0227] The shape of the positive electrode active material is not particularly limited, but is preferably particulate. The volume average particle diameter of the positive electrode active material is not particularly limited, but is preferably 0.1 to 50 μm. The volume average particle diameter of the positive electrode active material particles can be measured in the same manner as the volume average particle diameter of the negative electrode active material. The positive electrode active material obtained by the baking method may be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.
[0228] The positive electrode active material may be surface-coated with the above-mentioned surface coating agent, sulfur or phosphorus, or further with actinic rays, in the same manner as the negative electrode active material.
[0229] The positive electrode active material may be used alone or in combination of two or more kinds.
[0230] The electrode-forming composition may contain other components in addition to the lithium-based solid electrolyte, the inorganic solid electrolyte, and the active material. The electrode-forming composition may contain a conductive assistant. As the conductive assistant, a known one as a general conductive assistant can be used. As the conductive assistant, for example, graphites such as natural graphite and artificial graphite, which are electron conductive materials, carbon blacks such as acetylene black, ketjen black, and furnace black, amorphous carbon such as needle coke, fibrous carbon such as vapor-grown carbon fiber and carbon nanotube, and carbonaceous materials such as graphene and fullerene can be used. In addition, conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives can be used. In addition to the above conductive assistants, ordinary conductive assistants that do not contain carbon atoms, such as metal powder or metal fiber, may be used. In addition, a conductive additive is one that does not insert or release Li when the battery is charged and discharged, and does not function as an active material. Therefore, among conductive additives, those that can function as an active material in the active material layer when the battery is charged and discharged are classified as active materials rather than conductive additives. Whether or not a conductive additive functions as an active material when the battery is charged and discharged is not unique, but is determined by the combination with the active material.
[0231] Other components also include the binder and lithium salt described above.
[0232] The electrode-forming composition may contain a dispersion medium. Examples of the dispersion medium include water and various organic solvents.
[0233] The electrode-forming composition may contain, as components other than the above-mentioned components, an ionic liquid, a thickener, a crosslinking agent (one that undergoes a crosslinking reaction by radical polymerization, condensation polymerization, or ring-opening polymerization), a polymerization initiator (one that generates an acid or a radical by heat or light, etc.), a defoaming agent, a leveling agent, a dehydrating agent, and an antioxidant.
[0234] The method for forming the electrodes (negative electrode active material layer and positive electrode active material layer) using the electrode-forming composition is not particularly limited, but includes a method of forming an electrode by applying the electrode-forming composition. If necessary, the formed coating film may be subjected to a pressure treatment.
[0235] The method for applying the electrode-forming composition is not particularly limited, and examples thereof include spray application, spin coating, dip coating, slit coating, stripe coating, aerosol deposition, thermal spraying, and bar coating. After applying the electrode-forming composition, the resulting coating film may be dried as necessary. The drying temperature is not particularly limited, but the lower limit is preferably 30° C. or higher, more preferably 60° C. or higher, and even more preferably 80° C. or higher. The upper limit of the drying temperature is preferably 300° C. or lower, and more preferably 250° C. or lower.
[0236] The method for applying pressure to the coating film is not particularly limited, but examples include a method using a known press device (for example, a hydraulic cylinder press). The pressure applied during the pressure treatment is not particularly limited, but is preferably 5 to 1500 MPa, and more preferably 300 to 600 MPa. The time for the pressure treatment is not particularly limited, but from the viewpoint of productivity, it is preferably from 1 minute to 6 hours, and more preferably from 1 to 20 minutes. A heat treatment may be carried out during the pressure treatment. The heating temperature during the heat treatment is not particularly limited, but is preferably 30 to 300° C., and the heating time is preferably 1 minute to 6 hours. The atmosphere during pressurization is not particularly limited, and examples thereof include air, dry air (dew point of -20°C or lower), and an inert gas (eg, argon, helium, and nitrogen) atmosphere.
[0237] <Solid electrolyte sheet> The lithium-based solid electrolyte and inorganic solid electrolyte of the present invention may be contained in a solid electrolyte sheet. The solid electrolyte sheet is preferably used as a solid electrolyte sheet for an all-solid-state battery. The solid electrolyte sheet can be formed by forming the lithium-based solid electrolyte or inorganic solid electrolyte of the present invention into a sheet shape. The forming method is not particularly limited, and for example, a dispersion containing the lithium-based solid electrolyte or inorganic solid electrolyte of the present invention may be press-formed to form a sheet.
[0238] <Electrode sheet for all-solid-state secondary batteries> The lithium-based solid electrolyte and inorganic solid electrolyte of the present invention may be contained in an electrode sheet for an all-solid-state secondary battery. In particular, the lithium-based solid electrolyte of the present invention may be contained in an electrode sheet for an all-solid-state lithium-ion secondary battery. In the following, the electrode sheet for an all-solid-state lithium ion secondary battery will be mainly described in detail. The electrode sheet for an all-solid-state lithium-ion secondary battery of the present invention is a sheet-like molded article capable of forming an electrode active material layer of an all-solid-state lithium-ion secondary battery, and is preferably used for an electrode or a laminate of an electrode and a solid electrolyte layer.
[0239] The electrode sheet for an all-solid-state lithium-ion secondary battery of the present invention (also simply referred to as "electrode sheet") may be an electrode sheet having an active material electrode layer (hereinafter also simply referred to as "active material electrode layer") selected from the group consisting of a negative electrode active material layer and a positive electrode active material layer, and may be a sheet in which the active material electrode layer is formed on a substrate (current collector), or a sheet formed from an active material electrode layer without a substrate. This electrode sheet is usually a sheet having a current collector and an active material electrode layer, but it also includes an embodiment having a current collector, active material electrode layer, and solid electrolyte layer in this order, as well as an embodiment having a current collector, active material electrode layer, solid electrolyte layer, and active material electrode layer in this order. The electrode sheet of the present invention may have other layers as described above. The layer thickness of each layer constituting the electrode sheet of the present invention is the same as the layer thickness of each layer described in the all-solid-state lithium ion secondary battery described later. In the sheet for an all-solid-state lithium-ion secondary battery of the present invention, at least one active material electrode layer contains the lithium-based solid electrolyte of the present invention.
[0240] The method for producing the electrode sheet for an all-solid-state lithium ion secondary battery of the present invention is not particularly limited. For example, the electrode sheet can be produced by forming an active material electrode layer using the electrode-forming composition of the present invention. For example, there may be mentioned a method in which the electrode-forming composition is applied onto a current collector (with another layer interposed therebetween) to form a coating film, and then the coating film is subjected to a pressure treatment. As a method for applying the electrode-forming composition and a method for applying pressure to the coating film, the methods described in the section on the electrode-forming composition can be mentioned.
[0241] <All-solid-state secondary battery> The all-solid-state secondary battery of the present invention has a positive electrode active material layer, a negative electrode active material layer facing the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The positive electrode active material layer is preferably formed on a positive electrode current collector to constitute a positive electrode. The negative electrode active material layer is preferably formed on a negative electrode current collector to constitute a negative electrode. At least one of the negative electrode active material layer, the positive electrode active material layer, and the solid electrolyte layer contains the lithium-based solid electrolyte or inorganic solid electrolyte of the present invention, and preferably contains a lithium-based solid electrolyte. That is, the present invention also relates to an active material, and an electrode for an all-solid-state secondary battery having an active material layer containing the lithium-based solid electrolyte or inorganic solid electrolyte of the present invention, and a current collector. The following mainly describes in detail the all-solid-state lithium ion secondary battery of the present invention. The all-solid-state lithium-ion secondary battery of the present invention has a positive electrode active material layer, a negative electrode active material layer facing the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The positive electrode active material layer is preferably formed on a positive electrode current collector to constitute a positive electrode. The negative electrode active material layer is preferably formed on a negative electrode current collector to constitute a negative electrode. At least one of the negative electrode active material layer, the positive electrode active material layer, and the solid electrolyte layer contains the lithium-based solid electrolyte of the present invention.
[0242] The thickness of the negative electrode active material layer, the solid electrolyte layer, and the positive electrode active material layer is not particularly limited. In consideration of the dimensions of a general all-solid-state lithium ion secondary battery, the thickness of each layer is preferably 10 to 1000 μm, and more preferably 20 μm or more and less than 500 μm. It is more preferable that the thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is 50 μm or more and less than 500 μm. Each of the positive electrode active material layer and the negative electrode active material layer may include a current collector on the side opposite to the solid electrolyte layer.
[0243] The all-solid-state lithium ion secondary battery of the present invention may be used as an all-solid-state lithium ion secondary battery with the above-mentioned structure depending on the application, but it is preferable to further encapsulate it in a suitable case to make it into a dry cell. The case may be made of metal or resin (plastic). Examples of the metallic case include an aluminum alloy case and a stainless steel case. It is preferable that the metallic case is divided into a positive electrode case and a negative electrode case, and is electrically connected to the positive electrode current collector and the negative electrode current collector, respectively. It is preferable that the positive electrode case and the negative electrode case are joined and integrated via a gasket for preventing short circuit.
[0244] Hereinafter, an all-solid-state lithium ion secondary battery according to a preferred embodiment of the present invention will be described with reference to FIG. 7, but the present invention is not limited thereto. 7 is a cross-sectional view showing a schematic diagram of an all-solid-state lithium-ion secondary battery according to a preferred embodiment of the present invention. The all-solid-state lithium-ion secondary battery 10 of this embodiment has, from the negative electrode side, a negative electrode current collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode current collector 5, in this order. At least one of the negative electrode active material layer 2, the positive electrode active material layer 4, and the solid electrolyte layer 3 contains the lithium-based solid electrolyte of the present invention. Each layer is in contact with the other, forming an adjacent structure. By adopting such a structure, electrons (e - ) is supplied to the lithium ion (Li + During discharge, the lithium ions (Li + ) is returned to the positive electrode, and electrons are supplied to the operating part 6. In the illustrated example, a light bulb is used as a model for the operating part 6, and the light bulb is turned on by the discharge.
[0245] The negative electrode active material layer 2 contains the above-mentioned negative electrode active material. The positive electrode active material layer 4 contains the above-mentioned positive electrode active material.
[0246] The positive electrode current collector 5 and the negative electrode current collector 1 are preferably electronic conductors. Examples of materials for forming the positive electrode current collector include aluminum, aluminum alloys, stainless steel, nickel, and titanium, and aluminum or aluminum alloys are preferred. The positive electrode current collector may also include aluminum or stainless steel having a surface treated with carbon, nickel, titanium, or silver (a thin film formed thereon). Examples of materials for forming the negative electrode current collector include aluminum, copper, copper alloy, stainless steel, nickel, and titanium, and aluminum, copper, copper alloy, and stainless steel are preferred. Examples of the negative electrode current collector include aluminum, copper, copper alloy, and stainless steel whose surface is treated with carbon, nickel, titanium, or silver.
[0247] The current collector is usually in the form of a film sheet, but may be in other shapes. The thickness of the current collector is not particularly limited, but is preferably 1 to 500 μm. It is also preferable to provide the current collector surface with irregularities by surface treatment.
[0248] The method for producing the all-solid-state lithium ion secondary battery is not particularly limited, and may be any known method. Among them, the method using the electrode-forming composition and / or the solid electrolyte layer-forming dispersion liquid is preferred. For example, a positive electrode forming composition containing a positive electrode active material is applied onto a metal foil as a positive electrode current collector to form a positive electrode active material layer, then a solid electrolyte layer forming dispersion is applied onto this positive electrode active material layer to form a solid electrolyte layer, and then a negative electrode forming composition containing a negative electrode active material is applied onto the solid electrolyte layer to form a negative electrode active material layer, and a negative electrode current collector (metal foil) is laminated onto the negative electrode active material layer, and the resulting laminate is subjected to a pressure treatment to obtain an all-solid-state lithium ion secondary battery having a structure in which a solid electrolyte layer is sandwiched between a positive electrode active material layer and a negative electrode active material layer. This can also be enclosed in a case to form a desired all-solid-state lithium ion secondary battery. Also, the method of forming each layer can be reversed, so that a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer are formed on a negative electrode current collector, and then a positive electrode current collector is layered on top of the negative electrode active material layer, to produce an all-solid-state lithium ion secondary battery.
[0249] Alternatively, the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer may be separately produced and then laminated to produce an all-solid-state lithium ion secondary battery.
[0250] It is preferable to initialize the all-solid-state lithium ion secondary battery after production or before use. The initialization is not particularly limited, and can be performed, for example, by performing initial charging and discharging under a high pressing pressure, and then releasing the pressure until the pressure becomes the general use pressure of the all-solid-state lithium ion secondary battery.
[0251] <Applications of all-solid-state secondary batteries> The all-solid-state secondary battery of the present invention (particularly, the all-solid-state lithium ion secondary battery) can be applied to various applications. There is no particular limit to the application mode, but for example, when mounted on electronic devices, examples include notebook computers, pen-input personal computers, mobile personal computers, electronic book players, mobile phones, cordless phone sub-units, pagers, handheld terminals, mobile fax machines, mobile copiers, mobile printers, headphone stereos, video movie machines, liquid crystal televisions, handheld cleaners, portable CDs, mini-discs, electric shavers, transceivers, electronic organizers, calculators, memory cards, mobile tape recorders, radios, and backup power sources. Other consumer applications include automobiles, electric vehicles, motors, lighting equipment, toys, game equipment, road conditioners, watches, strobes, cameras, and medical equipment (pacemakers, hearing aids, shoulder massagers, etc.). Furthermore, it can be used for various military applications and space applications. It can also be combined with solar cells. EXAMPLES
[0252] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts, ratios, processing contents, and processing procedures shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0253] <Example 1> A lithium compound was obtained by ball milling Li2B4O7(247) powder (Rare Metallic) using a ball mill (Fritsch P-7) under the following conditions: Pot: stabilized zirconia (YSZ) (45 ml), grinding balls: stabilized zirconia (YSZ) (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), LBO powder (powdered Li2B4O7 crystal (Rare Metallic)): 1 g, atmosphere: air, ball mill treatment time: 100 hours. 0.05 g of Li(FSO2)2N(LiFSI) was added to the obtained lithium compound and further ball milled for 100 hours. The obtained powder was added to water so that the powder concentration was 42 mass %, and ultrasonically dispersed for 30 minutes. The resulting dispersion was then transferred to a glass petri dish and dried in air at 120° C. for 2 hours to obtain a film of a lithium-based solid electrolyte. The film was then peeled off to obtain a powder. The particle size distribution of the lithium-based solid electrolyte obtained above was about several μm to 10 μm, and the median diameter (D50) was 1.5 μm.
[0254] Using the lithium-based solid electrolyte obtained above, X-ray total scattering measurements were performed at SPring-8 BL04B2 (accelerating voltage: 61.4 keV, wavelength: 0.2019 Å). The samples were sealed in Kapton capillaries with 2 mm diameter or 1 mm diameter, and the experiments were performed. The obtained data was Fourier transformed as described above to obtain the reduced pair distribution function. As a result of the analysis, in the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement, in the range of r from 1 to 5 Å, a first peak was confirmed in which the peak top G(r) was 1.0 or more and the peak top was located at 1.43 Å, and a second peak was confirmed in which the peak top G(r) was 1.0 or more and the peak top was located at 2.40 Å. It was confirmed that the absolute value of G(r) in the range of r from more than 5 Å to 10 Å was less than 1.0 except for the regions of 3.50±0.2 Å, 3.99±0.2 Å, 5.85±0.2 Å, 6.20±0.2 Å, 7.25±0.2 Å, 9.50±0.2 Å, and 9.75±0.2 Å. From the above results, it was confirmed that the lithium-based solid electrolyte obtained by adding LiFSI and dispersing it in water was amorphous. On the other hand, the peaks attributable to the BO distance and the BB distance observed in general lithium tetraborate crystals were maintained in the lithium-based solid electrolyte. General lithium tetraborate crystals have a structure in which BO4 tetrahedra and BO3 triangles exist in a 1:1 ratio (diborate structure), and it was presumed that this structure was maintained in the lithium-based solid electrolyte.
[0255] The lithium-based solid electrolyte obtained above 7 The solid state of lithium-based solid electrolytes is compared with the full width at half maximum (FWHM1) of the peak that appears in the chemical shift range of -100 to +100 ppm in the spectrum obtained when Li-NMR measurement is performed at 20 °C. 7 The ratio of the full width at half maximum (FWHM2) of the peak appearing in the chemical shift range of -100 to +100 ppm in the spectrum obtained when Li-NMR measurement was performed at 120°C {(FWHM2 / FWHM1) × 100} was 33%. solid 7 When the spectrum obtained by Li-NMR measurement at 20°C was subjected to waveform separation of the first peak appearing in the range of -100 to +100 ppm, a second peak with a chemical shift in the range of -3 to 3 ppm and a full width at half maximum of 5 ppm or less was found, and the ratio of the area intensity of the second peak to the area intensity of the first peak was 4%.
[0256] Using the lithium-based solid electrolyte obtained above, infrared absorption spectroscopy was performed under the above-mentioned conditions. In the obtained infrared absorption spectrum, -1 The maximum absorption intensity in the wavenumber region of 3000 to 3500 cm -1 The ratio of the maximum absorption intensities in the wavenumber region was 0.72.
[0257] In the Raman spectrum of the obtained lithium-based solid electrolyte, -1 The coefficient of determination obtained by linear regression analysis using the least squares method in the wavenumber region was 0.9974. When the obtained lithium-based solid electrolyte was heated from 25° C. to 800° C. as described above, the mass loss rate was 29.8%.
[0258] Regarding the analysis of each element in the obtained lithium-based solid electrolyte, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC). N was estimated from the analyzed mass of sulfur taking into account the atomic weight of each element in the Li salt, and O was calculated by adding up the analyzed masses of elements other than O and calculating the difference from the total powder amount. The results are shown in the table below.
[0259] <Example 2> A lithium compound was obtained by ball milling Li2B4O7(247) powder (Rare Metallic) using a ball mill (Fritsch P-7) under the following conditions: Pot: stabilized zirconia (YSZ) (45 ml), grinding balls: stabilized zirconia (YSZ) (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), LBO powder (powdered Li2B4O7 crystal (Rare Metallic)): 1 g, atmosphere: air, ball mill treatment time: 100 hours. The obtained lithium compound was added to water at a powder concentration of 42 mass %, and ultrasonically dispersed for 30 minutes. Next, 0.05 g of Li(FSO2)2N(LiFSI) was added to the obtained dispersion and ultrasonically dispersed for another 30 minutes. The obtained dispersion was then transferred to a glass petri dish and dried at 120°C for 2 hours in air to obtain a film of a lithium-based solid electrolyte. The obtained film was then peeled off to obtain a powder. Using the obtained powder, various evaluations were carried out in the same manner as in Example 1. The results are summarized in the table below.
[0260] <Example 3> A ball mill (Fritsch P-7) was used to ball mill Li2B4O7(247) powder (Rare Metallic) under the following conditions: Pot: Stabilized Zirconia (YSZ) (45 ml), Milling ball: Stabilized Zirconia (YSZ) (average particle size: 5 mm, weight: 70 g), Rotation speed: 530 rpm (revolutions per minute), LBO powder (powdered Li2B4O7 crystal (Rare Metallic)) amount: 4.2 g, Atmosphere: Air, Ball mill treatment time: 100 hours to obtain a lithium compound. The obtained lithium compound was added to water at a powder concentration of 42% by mass and ultrasonically dispersed for 60 minutes to obtain solution 1. Next, 4.65 g of Li(FSO2)2N(LiFSI) was added to water at a powder concentration of 87 mass % and ultrasonically dispersed for 60 minutes to obtain solution 2. The obtained solutions 1 and 2 were mixed and stirred with a magnetic stirrer for 60 minutes. The obtained dispersion was then vacuum dried at 40° C. and 10 Pa for 15 hours to obtain a powder, which was then used for various evaluations in the atmosphere in the same manner as in Example 1. The results are summarized in the table below.
[0261] <Example 4> A ball mill (Fritsch P-7) was used to ball mill Li2B4O7(247) powder (Rare Metallic) under the following conditions: Pot: Stabilized Zirconia (YSZ) (45 ml), Milling ball: Stabilized Zirconia (YSZ) (average particle size: 5 mm, weight: 70 g), Rotation speed: 530 rpm (revolutions per minute), LBO powder (powdered Li2B4O7 crystal (Rare Metallic)) amount: 4.2 g, Atmosphere: Air, Ball mill treatment time: 100 hours to obtain a lithium compound. The obtained lithium compound was added to water at a powder concentration of 42% by mass and ultrasonically dispersed for 60 minutes to obtain solution 3. Next, 3.67 g of Li(FSO2)2N(LiFSI) was added to water at a powder concentration of 87 mass % and ultrasonically dispersed for 60 minutes to obtain solution 4. The obtained solutions 3 and 4 were mixed and stirred with a magnetic stirrer for 60 minutes. The obtained dispersion was then vacuum dried at 40° C. and 10 Pa for 15 hours to obtain a powder, which was then used for various evaluations in the atmosphere in the same manner as in Example 1. The results are summarized in the table below.
[0262] <Example 5> A ball mill (Fritsch P-7) was used to ball mill Li2B4O7(247) powder (Rare Metallic) under the following conditions: Pot: Stabilized Zirconia (YSZ) (45 ml), Milling ball: Stabilized Zirconia (YSZ) (average particle size: 5 mm, weight: 70 g), Rotation speed: 530 rpm (revolutions per minute), LBO powder (powdered Li2B4O7 crystal (Rare Metallic)) amount: 4.2 g, Atmosphere: Air, Ball mill treatment time: 100 hours to obtain a lithium compound. The obtained lithium compound was added to water at a powder concentration of 42% by mass and ultrasonically dispersed for 60 minutes to obtain solution 5. Next, 7.13 g of Li(F3CSO2)2N(LiTFSI) was added to water at a powder concentration of 87 mass % and ultrasonically dispersed for 60 minutes to obtain solution 6. The obtained solutions 5 and 6 were mixed and stirred with a magnetic stirrer for 60 minutes. The obtained dispersion was then vacuum dried at 40° C. and 10 Pa for 15 hours to obtain a powder, which was then used for various evaluations in the atmosphere in the same manner as in Example 1. The results are summarized in the table below. In Example 5, the carbon amounts shown in Table 2 described later were estimated from the analyzed mass of sulfur, taking into account the weight of each atom in the Li salt.
[0263] <Comparative Example 1> Powdered Li2B4O7 crystals (LBO powder) (made by Rare Metallic) (crystal powder) were compacted at 27℃ (room temperature) under an effective pressure of 220MPa to obtain a compact for comparison. The ionic conductivity of the obtained compact could not be detected.
[0264] <Reference example> A ball mill (Fritsch P-7) was used to ball mill Li2B4O7 (LBO) powder (Rare Metallic) under the following conditions: Pot: stabilized zirconia (YSZ) (45 ml), milling balls: stabilized zirconia (YSZ) (average particle size: 5 mm, number: 50), rotation speed: 500 rpm (revolutions per minute), LBO powder (powdered Li2B4O7 crystal (Rare Metallic)) amount: 2 g, atmosphere: air, ball mill treatment time: 100 hours, to obtain a lithium compound. Using the obtained lithium compound, various evaluations were performed in the same manner as in Example 1.
[0265] The particle size distribution of the obtained lithium compound was about several μm to 10 μm, and the median diameter (D50) was 1.5 μm. The bulk modulus of the obtained lithium compound was 36 GPa. The bulk modulus of the LBO powder before the ball mill treatment was 47 GPa. The measurement of the bulk modulus of the lithium compound was carried out by the ultrasonic attenuation method. Specifically, first, a suspension was prepared by suspending the lithium compound in pure water. The content of the lithium compound in the suspension was 1.2% by mass with respect to the total mass of the suspension. Next, the ultrasonic attenuation spectrum of the suspension was measured, and the bulk modulus of the lithium compound (GPa) was obtained by fitting with the scattering attenuation theory. When calculating the bulk modulus, the density of the specific solid electrolyte was set to 2.3 g / mL, and the Poisson's ratio was set to 0.12, and fitting was performed. In addition, with regard to the fitting with the scattering attenuation theory, the bulk modulus was calculated using the formulas (7), (12), and (13) described in Kohjiro Kubo et al., Ultrasonics 62 (2015) pp. 186-194.
[0266] <Various evaluations (part 1)> (Ionic conductivity measurement) The lithium-based solid electrolyte obtained in each Example was compacted at 27°C (room temperature) under an effective pressure of 220 MPa to obtain a green compact. Indium foil was placed on the front and back of the obtained green compact, and the ionic conductivity was estimated from the analysis of the arc diameter of the Cole-Cole plot (Nyquist plot) obtained by AC impedance measurement via two In electrodes (measurement temperature 27°C or 60°C, applied voltage 50 mV, measurement frequency range 1 Hz to 1 MHz).
[0267] (X-ray total scattering measurement) X-ray total scattering measurements were performed at SPring-8 BL04B2 (accelerating voltage: 61.4 keV, wavelength: 0.2019 Å) using the lithium-based solid electrolyte of the example, the crystal powder of the comparative example, and the lithium compound of the reference example. The samples were sealed in Kapton capillaries of 2 mmφ or 1 mmφ, and the experiments were performed. The obtained data was Fourier transformed as described above to obtain the reduced pair distribution function. As a result of the analysis, in the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement, if there exists a first peak whose peak top is located in the range of r 1.43±0.2 Å and a second peak whose peak top is located in the range of r 2.40±0.2 Å, and the G(r) of the peak top of the first peak and the G(r) of the peak top of the second peak are greater than 1.0, the "short-distance G(r)" column in Table 3 is marked as "A", and otherwise it is marked as "B". In Examples 1 to 4 shown in Table 3 below and Examples 8 to 12 shown in Table 6 below, the G(r) value at the peak top of the first peak was 1.2 or more. In addition, in the above reduced pair distribution function G(r), when the absolute value of G(r) is less than 1.0 in the range of r exceeding 5 Å and not exceeding 10 Å, the “long-distance G(r)” column in Table 3 is marked with “A”, and in other cases it is marked with “B”.
[0268] (X-ray diffraction measurement) X-ray diffraction measurements were carried out using CuKα radiation on the lithium-based solid electrolyte of the example, the crystalline powder of the comparative example, and the lithium compound of the reference example under the measurement conditions of 0.01° / step and 3° / min. As a result of the measurement, the diffraction pattern obtained was rated as "A" if it satisfied the above-mentioned requirement Y, and rated as "B" if it did not. In addition, in Examples 1 to 5 shown in Table 3 below, and Examples 6 to 13 shown in Table 6 below, the first peak, the second peak, the third peak, and the fourth peak were not present in the X-ray diffraction pattern, or the intensity ratio of at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak was 2.0 or less.
[0269] In Table 1, the "elemental analysis" column shows the molar amount of each element in the composition of the lithium-based solid electrolyte obtained in each Example, as a relative value with the Li content set to "1.00." In Table 2, the "elemental analysis" column shows the molar amount of each element in the composition of the lithium-based solid electrolyte obtained in each Example, as a relative value with the content of B set to "4.00." In the table, the "Percentage of Full Width at Half Maximum (%)" column indicates the solid state of the lithium-based solid electrolyte. 7 The solid state of lithium-based solid electrolytes is shown in Fig. 1. The solid state of lithium-based solid electrolytes is shown in Fig. 1. The solid state of lithium-based solid electrolytes is shown in Fig. 1. 7 This represents the percentage (%) of the full width at half maximum of the peak appearing in the chemical shift range of -100 to +100 ppm in the spectrum obtained when Li-NMR measurement was performed at 120°C.
[0270] In the table, the "Ratio of area intensity" column indicates the ratio of the area intensity of the second peak to the area intensity of the first peak, as described above. The "Numeric value (%)" column indicates a specific numerical value, and the "Range" column indicates to which range the numerical value of each Example and Comparative Example belongs according to the following criteria (range of area intensity ratio). Note that in Examples 4 and 5, no numerical value is shown in the "Numeric value (%)" column, and the "Range" column indicates which range it falls within. (Percentage range of area intensity) A: When the area intensity ratio is 15% or more B: When the area intensity ratio is 0.5% or more and less than 15% C: When the area intensity ratio is less than 0.5%
[0271] In the table, the "maximum absorption intensity ratio" column indicates the maximum absorption intensity ratio between 800 and 1600 cm in the infrared absorption spectrum of lithium-based solid electrolytes. -1 The maximum absorption intensity in the wavenumber region of 3000 to 3500 cm -1 The "Numeric value" column shows a specific numerical value, and the "Range" column shows the range to which the numerical value of each Example and Comparative Example belongs according to the following criteria (range of maximum absorption intensity ratio). Note that in Examples 4 and 5, no numerical value is shown in the "Numeric value" column, and the "Range" column shows the range to which the numerical value belongs. (Maximum absorption intensity ratio range) A: When the maximum absorption intensity ratio is 0.20 or more B: When the maximum absorption intensity ratio is less than 0.20
[0272] In the table, the column "Maximum absorption intensity ratio (heated at 90°C under N2 atmosphere)" indicates that the obtained lithium-based solid electrolyte was heated at 90°C for 5 minutes, and then the infrared absorption spectrum of the lithium-based solid electrolyte after the heat treatment was measured. -1 The maximum absorption intensity in the wavenumber region of 3000 to 3500 cm -1 This represents the ratio of maximum absorption intensity in the wave number region of In the table, the “coefficient of determination” column indicates the coefficient of determination from 600 to 850 cm of the Raman spectrum for Examples 1 and 2. -1 The coefficient of determination is obtained by performing linear regression analysis using the least squares method in the wavenumber domain. In the table, in the "Requirement T" column, the case where the above-mentioned requirement T is satisfied is indicated as "A", and the case where it is not satisfied is indicated as "B". In the Raman spectra of the lithium-based solid electrolytes of Examples 1 to 5, the peak intensity in the range of 710 to 730 cm defined by requirement T was -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The first peak above, 770-790 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 The second peak above and 1020-1040 cm -1 The peak top is at 5 cm and the full width at half maximum is 5 cm. -1 None of the above third peaks were present. In the table, the column "mass reduction rate (%)" indicates the mass reduction rate when the above-mentioned lithium-based solid electrolyte was heated to 800°C. In the table, "-" means that the measured value is not shown.
[0273] In addition, in Examples 1 to 5, all of the lithium compounds obtained by ball milling Li2B4O7(247) powder (manufactured by Rare Metallic) satisfied the above-mentioned requirements S1 to S3. More specifically, in Examples 1 to 5, the Raman spectrum of the lithium compound obtained by ball milling Li2B4O7(247) powder (manufactured by Rare Metallic) did not contain any of the first to third peaks specified in requirement S2. In addition, in Examples 1 to 5, the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of the lithium compound obtained by ball milling Li2B4O7(247) powder (manufactured by Rare Metallic) did not have any of the first to fourth peaks specified in requirement S3, or had at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak, and the intensity ratio calculated by at least one intensity measurement method of the specific peak was 2.0 or less.
[0274] In addition, in Examples 1 to 5, the lithium compounds obtained by ball milling Li2B4O7(247) powder (manufactured by Rare Metallic) satisfied the requirement W. In addition, in Examples 1 to 5, the lithium compounds obtained by ball milling Li2B4O7 (247) powder (made by Rare Metallic) satisfied requirement V. More specifically, in Examples 1 to 5, in the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of the lithium compounds obtained by ball milling Li2B4O7 (247) powder (made by Rare Metallic), none of the first peak to the fourth peak specified in requirement S3 was present, or at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak was present, and the intensity ratio calculated by at least one intensity measurement method of the specific peak was 2.0 or less. In addition, in Examples 1 to 5, the lithium compounds obtained by ball milling Li2B4O7(247) powder (made by Rare Metallic) satisfied the requirement T2. More specifically, in the Raman spectrum of the lithium compounds obtained by ball milling Li2B4O7(247) powder (made by Rare Metallic) in Examples 1 to 5, none of the first peak to the third peak specified in the requirement T2 was present.
[0275] [Table 1]
[0276] [Table 2]
[0277] [Table 3]
[0278] As shown in the above table, the lithium-based solid electrolyte of the present invention exhibited the desired effects. In particular, the invention described in Patent Document 1 has an ionic conductivity of 10 -5 S cm -1 It was confirmed that the ionic conductivity of the present invention was superior to that of the conventional polymer. As shown in Table 2, it was confirmed that the Li content in Example 3 was higher. The reason for the increase in Li content is presumably because, in Example 3, a method of mixing an aqueous solution containing a mechanically milled lithium compound with an aqueous solution containing a lithium salt (method 3 in step 2B described above) is carried out, and this method allows the mixing amount of Li(FSO2)2N (LiFSI) to be increased, so the amount of Li taken up in the lithium-based solid electrolyte is increased. It was also confirmed that ionic conductivity was improved in Example 3. The reason for the improvement in ionic conductivity is presumably because the Li composition ratio (content ratio) increases, and the increased Li contains Li with high mobility, resulting in an overall increase in Li with high mobility.
[0279] In addition, as shown in the "Maximum absorption intensity ratio" and "Maximum absorption intensity ratio (under N2 atmosphere, heated at 90°C)" columns of Table 3, in Example 3, the absorption intensity ratio of 800 to 1600 cm was increased by the heat treatment. -1 The maximum absorption intensity in the wavenumber region of 3000 to 3500 cm -1 The ratio of maximum absorption intensities in the wavenumber region of 100 to 1500 was decreased. This is presumably due to the volatilization of free water contained in the lithium-based solid electrolyte.
[0280] In the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement of the crystal powder of Comparative Example 1, there was a first peak (corresponding to BO proximity) with a peak top located at 1.40 Å and a second peak (corresponding to BB proximity) with a peak top located at 2.40 Å, and the G(r) of the peak tops of the first and second peaks was 1.0 or more (see FIG. 12). In addition, there were peaks with peak tops located at 3.65 Å, 5.22 Å, 5.51 Å, and 8.54 Å, and the G(r) of the peak tops of each peak was 1.0 or more (see FIG. 12). In contrast, the reduced pair distribution function G(r) obtained from the X-ray total scattering measurement of the lithium compound of the Reference Example had a first peak (corresponding to the BO proximity) with a peak top located at 1.40 Å and a second peak (corresponding to the BB proximity) with a peak top located at 2.40 Å, and the G(r) of the peak tops of the first and second peaks was 1.0 or more. On the other hand, the absolute value of G(r) was less than 1.0 when r was in the range of more than 5 Å and not more than 10 Å. These results confirmed that mechanical milling treatment reduces the peaks of long-range ordered structures in the range of r greater than 5 Å and less than 10 Å. On the other hand, the peaks attributable to the B-O and B-B distances observed in typical lithium tetraborate crystals were maintained even after mechanical milling treatment. From these results, it is believed that mechanical milling treatment maintains the structure (diborate structure) in which BO4 tetrahedra and BO3 triangles exist in a 1:1 ratio, which is present in typical lithium tetraborate crystals.
[0281] FIG. 13 shows the X-ray diffraction pattern of the crystalline powder of Comparative Example 1. As shown in FIG. 13, Comparative Example 1 did not satisfy the above-mentioned requirement Y, and multiple narrow peaks were observed. More specifically, the strongest peak corresponding to the (1,1,2) plane was observed at a 2θ value of 21.78°. Other major diffraction peaks were a peak corresponding to the (2,0,2) plane at 25.54°, a peak corresponding to the (2,1,3) plane at 33.58°, and a peak corresponding to the (3,1,2) plane at 34.62°, and the intensities of these three peaks were almost equal. These peaks are derived from crystalline components. In contrast, Figure 14 shows the X-ray diffraction pattern of the lithium-based solid electrolyte of Example 3. As shown in Figure 14, in Example 3, even if the intensity ratio 5.0 specified in the above-mentioned requirement Y was changed to 2.0, the requirement was met. It can be seen that the crystalline components present in Figure 13 were amorphized by the mechanical milling treatment, and the sharp peaks derived from lithium tetraborate crystals disappeared and became broader.
[0282] <Evaluation (part 2)> The lithium-based solid electrolyte powder compact (pellet) (10 mmφ, 0.9 mmt) obtained in Example 3 was vacuum-dried at 27° C. under a restraint of 60 MPa, and the pressure change and ionic conductivity with respect to the vacuum drying time were evaluated. The method for producing the green compact and the evaluation of the ionic conductivity were the same as those described in (Ionic Conductivity Measurement) of <Various Evaluations (Part 1)> above, except that the In electrode was changed to a Ti electrode. The results are shown in Table 4.
[0283] [Table 4]
[0284] The lithium-based solid electrolyte of Example 3 has an infrared absorption spectrum of 3000 to 3500 cm -1 The OH stretching peak of the OH group increases, suggesting the presence of many OH groups and water. In addition, the presence of free water and water in a different state from free water is also suspected. In the above evaluation, in order to confirm the presence of substances with good ionic conductivity other than free water, the pellets were first dried by vacuum drying under conditions that were thought to volatilize the free water, and then further dried under conditions with increased strength, and the ionic conductivity at each stage was evaluated.
[0285] As shown in Table 4, the drying time was 5 minutes, the pressure was 200 Pa, and the free water was considered to be in a vaporized state. However, the ionic conductivity was 3.8 × 10 -3 Even with a drying time of 1080 minutes and a pressure of 15 Pa, the ionic conductivity was 5.7×10 -4 It was found that the ionic conductivity of the water was 0.05 S / cm, confirming the existence of a substance with good ionic conductivity other than free water. Although the nature of this substance is not clear, it is assumed to be water in a different state from free water. In addition, although the phenomenon that occurs during the drying process is not clear, as shown in Table 4, the pressure was 10 Pa after a drying time of 50 minutes, and it is presumed that under these conditions water in a state different from free water remains and that this water gradually desorbs; furthermore, the pressure was 15 Pa after a drying time of 1,080 minutes, and it is presumed that two types of water in a state different from free water exist and that water that is less likely to volatilize remains. The above results suggest that the lithium-based solid electrolyte contains water in a state different from free water, which has good ionic conductivity, because the electrolyte showed excellent ionic conductivity even after the drying time was extended.
[0286] <Example 6> A ball mill (Fritsch P-7) was used to ball mill Li2B4O7(247) powder (Rare Metallic) under the following conditions: Pot: Stabilized Zirconia (YSZ) (45 ml), Milling ball: Stabilized Zirconia (YSZ) (average particle size: 5 mm, weight: 70 g), Rotation speed: 530 rpm (revolutions per minute), LBO powder (powdered Li2B4O7 crystal (Rare Metallic)) amount: 4.2 g, Atmosphere: Air, Ball mill treatment time: 100 hours to obtain a lithium compound. The obtained lithium compound was added to water at a powder concentration of 42 mass%, and ultrasonically dispersed for 60 minutes to obtain solution 7. Next, 7.12 g of Li(F3CSO2)2N(LiTFSI) was added to water at a powder concentration of 87 mass % and ultrasonically dispersed for 60 minutes to obtain solution 8. The obtained solutions 7 and 8 were mixed and stirred with a magnetic stirrer for 60 minutes. The obtained dispersion was then vacuum dried at 40° C. and 10 Pa for 15 hours to obtain a lithium-based solid electrolyte. Various evaluations were carried out in the atmosphere in the same manner as in Example 1.
[0287] <Example 7> A lithium-based solid electrolyte was obtained in the same manner as in Example 6, except that the contents of water and Li(F3CSO2)2N(LiTFSI) in the obtained lithium-based solid electrolyte were changed to the amounts shown in the table below, and various evaluations were performed under air in the same manner as in Example 1.
[0288] <Examples 8 to 13> A lithium-based solid electrolyte was obtained in the same manner as in Example 6, except that Li(F3CSO2)2N (LiTFSI) was changed to Li(FSO2)2N (LiFSI) and the contents of water and Li(FSO2)2N (LiFSI) in the obtained lithium-based solid electrolyte were changed to the amounts shown in the table below. Various evaluations were performed under air in the same manner as in Example 1.
[0289] In Table 5, the "BM-LBO247", "Li salt", and "Water" columns indicate the relative molar ratios of each component in the powder obtained in each Example and Reference Example. Specifically, "BM-LBO247" indicates ball milled Li2B4O7, and "Li salt" indicates the lithium salt (Li(F3CSO2)2N(LiTFSI), Li(FSO2)2N(LiFSI)) used in each Example, and the table indicates the relative molar ratios of each component when the molar amount of BM-LBO247 is 1. For example, in the powder obtained in Example 6, the molar ratio of Li salt to BM-LBO247 is 1, and the molar ratio of water to BM-LBO247 is 12. The above molar ratio was calculated by the following method. Regarding the analysis of each element in the obtained powder, lithium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC). N was estimated from the analyzed mass of sulfur taking into account the weight of each atom in the Li salt, and O was calculated as the difference from the total powder weight by adding up the analyzed masses of elements other than O. In Examples 6 and 7, the amount of carbon was estimated from the analyzed mass of sulfur taking into account the weight of each atom in the Li salt. The molar ratio of BM-LBO247 to Li salt in the powder was calculated from the molar ratio of an element only present in BM-LBO247 (e.g., B) to an element only present in Li salt (e.g., a specific element). The molar ratio of BM-LBO247 to water was calculated by subtracting the molar ratio of O contained in BM-LBO247 and Li salt from the molar ratio of O in the powder to calculate the molar amount of O derived from water, and then using the resulting molar amount of O derived from water and the molar amount of BM-LBO247.
[0290] In addition, in Examples 6 to 13, all of the lithium compounds obtained by ball milling Li2B4O7(247) powder (manufactured by Rare Metallic) satisfied the above-mentioned requirements S1 to S3. More specifically, in Examples 6 to 13, the Raman spectrum of the lithium compound obtained by ball milling Li2B4O7(247) powder (manufactured by Rare Metallic) did not contain any of the first to third peaks specified in requirement S2. In addition, in Examples 6 to 13, the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of the lithium compound obtained by ball milling Li2B4O7(247) powder (manufactured by Rare Metallic) did not have any of the first to fourth peaks specified in requirement S3, or had at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak, and the intensity ratio calculated by at least one intensity measurement method of the specific peak was 2.0 or less.
[0291] In addition, in Examples 6 to 13, the lithium compounds obtained by ball milling Li2B4O7(247) powder (manufactured by Rare Metallic) satisfied the requirement W. In addition, in Examples 6 to 13, the lithium compounds obtained by ball milling Li2B4O7 (247) powder (made by Rare Metallic) satisfied requirement V. More specifically, in Examples 6 to 13, in the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation of the lithium compounds obtained by ball milling Li2B4O7 (247) powder (made by Rare Metallic), none of the first peak to the fourth peak specified in requirement S3 was present, or at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak was present, and the intensity ratio calculated by at least one intensity measurement method of the specific peak was 2.0 or less. In addition, in Examples 6 to 13, the lithium compounds obtained by ball milling Li2B4O7 (247) powder (made by Rare Metallic) satisfied the requirement T2. More specifically, in Examples 6 to 13, the Raman spectrum of the lithium compounds obtained by ball milling Li2B4O7 (247) powder (made by Rare Metallic) did not have any of the first to third peaks specified in the requirement T2.
[0292] In the Raman spectra of the lithium-based solid electrolytes of Examples 6 to 13, none of the first to third peaks specified by requirement T was present.
[0293] [Table 5]
[0294] [Table 6]
[0295] As shown in the above table, the lithium-based solid electrolyte of the present invention exhibited the desired effects.
[0296] In addition, a lithium-based solid electrolyte was prepared in the same manner as in Example 3, except that LiB3O5 was used instead of the Li2B4O7(247) powder used in Example 3. In addition, X-ray total scattering measurements were performed on ball-milled LiB3O5 instead of Li2B4O7(247) powder, and on a lithium-based solid electrolyte obtained using LiB3O5, and it was confirmed that they satisfied the above-mentioned requirements X2 and X5, respectively. In addition, instead of the Li2B4O7(247) powder used in Example 3, Li3B 11 O 18 A lithium-based solid electrolyte was produced in the same manner as in Example 3, except that the following was used: In addition, ball-milled Li3B was used instead of Li2B4O7(247) powder. 11 O 18 , and Li3B 11 O 18 When the lithium-based solid electrolyte obtained by using the method was subjected to X-ray total scattering measurement, it was confirmed that the above-mentioned requirements X3 and X5 were satisfied. In addition, instead of the Li2B4O7(247) powder used in Example 3, Li3B7O 12 A lithium-based solid electrolyte was produced in the same manner as in Example 3, except that the following was used: Note that ball-milled Li3B7O was used instead of Li2B4O7(247) powder. 12 , and Li3B7O 12 When the lithium-based solid electrolyte obtained by using the method was subjected to X-ray total scattering measurement, it was confirmed that the above-mentioned requirements X4 and X5 were satisfied.
[0297] In addition, the ball milled LiB3O5 and the lithium-based solid electrolyte obtained using LiB3O5 satisfied the above-mentioned requirements Y2 and Y5, respectively, in the X-ray diffraction patterns obtained from X-ray diffraction measurements using CuKα radiation. More specifically, in the X-ray diffraction patterns of the ball milled LiB3O5 and the lithium-based solid electrolyte obtained using LiB3O5, none of the first to fourth peaks specified in the requirements Y2 and Y5 above is present, or at least one specific peak selected from the group consisting of the first, second, third and fourth peaks is present, and the intensity ratio of at least one of the specific peaks calculated by an intensity measurement method is 2.0 or less.
[0298] Ball-milled Li3B 11 O 18 , and Li3B 11 O 18 The lithium-based solid electrolyte obtained by using the above satisfied the above-mentioned requirements Y3 and Y6 in the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation. More specifically, the ball milled Li3B 11 O 18 , and Li3B 11 O 18 In the X-ray diffraction pattern of the lithium-based solid electrolyte obtained using the above, none of the first peak to the fourth peak as specified in the above requirements Y3 and Y6 was present, or at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak was present, and the intensity ratio of at least one of the specific peaks calculated by an intensity measurement method was 2.0 or less.
[0299] Ball-milled Li3B7O 12 , and Li3B7O 12 The lithium-based solid electrolyte obtained by using the above satisfied the above-mentioned requirements Y4 and Y7 in the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα radiation. More specifically, the ball milled Li3B7O 12 , and Li3B7O 12In the X-ray diffraction pattern of the lithium-based solid electrolyte obtained using the above, none of the first peak to the fourth peak as specified in the above requirements Y4 and Y7 was present, or at least one specific peak selected from the group consisting of the first peak, the second peak, the third peak, and the fourth peak was present, and the intensity ratio of at least one of the specific peaks calculated by an intensity measurement method was 2.0 or less. [Explanation of symbols]
[0300] 1 Negative electrode current collector 2 Negative electrode active material layer 3 Solid electrolyte layer 4 Cathode active material layer 5 Positive electrode current collector 6. Working Parts 10 All-solid-state lithium-ion secondary battery
Claims
1. A lithium-based solid electrolyte comprising amorphous lithium tetraborate, water, and a lithium salt, the molar ratio of the water to the lithium tetraborate being 3 to 15.
2. A lithium-based solid electrolyte comprising mechanically milled lithium tetraborate, water, and a lithium salt, the molar ratio of the water to the lithium tetraborate being 3-15.
3. 2. The lithium-based solid electrolyte of claim 1, wherein the molar ratio of the lithium salt to the lithium tetraborate is 0.001 to 1.
5.
4. 3. The lithium-based solid electrolyte of claim 2, wherein the molar ratio of the lithium salt to the lithium tetraborate is 0.001 to 1.
5.
5. The lithium-based solid electrolyte according to any one of claims 1 to 4, wherein the lithium salt is a compound represented by formula (1). Formula (1) LiN(R f1 SO 2 ) (R f2 SO 2 ) R f1 and R f2 each independently represents a fluorine atom or a perfluoroalkyl group.
6. In the infrared absorption spectrum, 800 to 1600 cm -1 3000 to 3500 cm for the maximum absorption intensity in the wave number region -1 The lithium-based solid electrolyte according to any one of claims 1 to 5, wherein the ratio of maximum absorption intensity in the wave number region of is 1 / 5 or more.
7. solid 7 The solid Li-NMR spectrum was measured at 20° C. and the chemical shift in the spectrum was measured in the range of −100 to +100 ppm. 7 The lithium-based solid electrolyte according to any one of claims 1 to 6, wherein the ratio of the full width at half maximum of a peak appearing in the chemical shift range of -100 to +100 ppm in a spectrum obtained by Li-NMR measurement at 120 ° C. is 50% or less.
8. The lithium-based solid electrolyte according to any one of claims 1 to 7, wherein, when a first peak appearing in the range of -100 to +100 ppm in a spectrum obtained by performing solid-state Li-NMR measurement at 20 ° C. is subjected to waveform separation, the lithium-based solid electrolyte has a second peak having a chemical shift in the range of -3 to 3 ppm and a full width at half maximum of 5 ppm or less, and the ratio of the area intensity of the second peak to the area intensity of the first peak is 0.5% or more.
9. A method for producing a lithium-based solid electrolyte according to any one of claims 1 to 8, Step 1 of subjecting a lithium-based oxide containing Li and B to mechanical milling treatment; Step 2 of mixing the product obtained in step 1 with water; and a step 3 of removing water from the dispersion obtained in the step 2 to obtain a lithium-based solid electrolyte. A method for producing a lithium-based solid electrolyte that satisfies any one of the following requirements 1 to 3: Requirement 1: The mechanical milling treatment in step 1 is carried out in the presence of a specific element source containing two or more elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H, and N. Requirement 2: In the step 2, the product, water, and the specific element source are mixed together. Requirement 3: In the step 3, the product obtained by removing water from the dispersion obtained in the step 2 is mixed with the specific element source to obtain the lithium-based solid electrolyte.
10. Satisfying the above requirement 1, 10. The method for producing a lithium-based solid electrolyte according to claim 9, further comprising, before the step 1, a step 0 of subjecting a lithium-based oxide containing Li and B to a mechanical milling treatment in an environment in which the specific element source is not present.
11. A positive electrode active material and a coating layer disposed on the positive electrode active material, The modified cathode active material, wherein the coating layer comprises the lithium-based solid electrolyte according to any one of claims 1 to 8.
12. A negative electrode active material and a coating layer disposed on the negative electrode active material, The coating layer comprises the lithium-based solid electrolyte according to any one of claims 1 to 8.
13. An all-solid-state secondary battery including a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer in this order, At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer contains the lithium-based solid electrolyte according to any one of claims 1 to 8.
14. An electrode sheet for an all-solid-state secondary battery, comprising the lithium-based solid electrolyte according to any one of claims 1 to 8.
15. A solid electrolyte sheet comprising the lithium-based solid electrolyte according to any one of claims 1 to 8.
16. An active material layer comprising an active material and the lithium-based solid electrolyte according to any one of claims 1 to 8; A current collector; Electrode for all-solid-state secondary batteries.
Citation Information
Patent Citations
Electrolyte particles
JP2009215130A
Lithium ion-conducting material
JP2018052755A
All-solid-state battery including a solid electrolyte and an ion-conducting material layer
JP2019506706A
Multilayer electrodes and solid electrolytes
WO2020053267A1